Resist pattern coating composition

JP7609750B2Active Publication Date: 2025-01-07NISSAN CHEM CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021162320
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2015-12-21
Filing Date
2021-09-30
Publication Date
2025-01-07
Estimated Expiration
2036-05-20

AI Technical Summary

Benefits of technology

【0012】 本発明のパターン形成用ポリマーを含む塗布組成物は、マスク露光後、レジストの現像中または現像後に、レジスト表面に接触させ、該ポリマーでレジストパターン間を充填することにより、レジストパターンの倒壊を防ぐことができる。その後、レジストパターン間が該ポリマーで充填された表面をドライエッチングし、レジストパターンを除去すると、充填されたポリマーが新たなレジストパターンとなる。本発明はこのリバースプロセスにより倒壊しない微細なパターンを形成することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609750000001
    Figure 0007609750000001
  • Figure 0007609750000002
    Figure 0007609750000002
  • Figure 0007609750000003
    Figure 0007609750000003
Patent Text Reader

Abstract

A composition is provided that can be applied to a resist pattern to reverse the pattern by utilizing a difference in gas etching rates. [Solution] A composition comprising the following components (A) and (B), which is applied to a resist pattern to reverse the pattern by utilizing a difference in gas etching rate: Component (A): at least one compound selected from the group consisting of hydrolyzable silanes (a4), hydrolyzates of the hydrolyzable silanes (a5), and hydrolyzed condensates of the hydrolyzable silanes (a6); (B) component: aqueous solvent, The hydrolyzable silane (a4) includes a hydrolyzable silane (i) containing an organic group having a tertiary amino group, a hydrolyzable silane (ii) containing an organic group having an ionic functional group, or a hydrolyzable silane (iii) containing an organic group having a hydroxyl group; The hydrolyzate of the hydrolyzable silane (a4) is obtained by hydrolyzing the hydrolyzable silane (a4) in the presence of an alkaline substance or an acidic substance. The composition.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coating composition for coating a resist pattern in the process of being formed from a resist during development by a lithography process, or to a resist pattern after development, and to a technique for reversing a pattern by coating the coating composition, filling the resist pattern with the coating composition, and then etching away the resist by dry etching or the like. [Background technology]

[0002] In recent years, as patterns become finer, the phenomenon of patterns collapsing during the development and developer rinsing processes carried out after exposure of the resist in the lithography process has become a problem. The cause of this pattern collapse is believed to be the Laplace force, which acts between patterns due to the surface tension and the flow of the liquid when the developer or rinse solution dries. It is also believed that the Laplace force is generated when the developer or rinse solution is blown outward by centrifugal force, which causes the pattern collapse. In order to solve such problems, a pattern forming method has been disclosed, which includes the steps of forming a resist film on a substrate, selectively irradiating the resist film with energy rays to form a latent image in the resist film, supplying a developer (alkaline developer) onto the resist film to form a resist pattern from the resist film on which the latent image has been formed, supplying a rinse liquid onto the substrate to replace the developer on the substrate with a rinse liquid, supplying a coating film material onto the substrate to replace the rinse liquid on the substrate with a coating film material containing at least a part of the solvent of the rinse liquid and a solute different from the resist film, volatilizing a solvent in the coating film material to form a coating film covering the resist film on the substrate, receding at least a part of the surface of the coating film to expose at least a part of the upper surface of the resist pattern and to form a mask pattern composed of the coating film, and processing the substrate using the mask pattern (see Patent Document 1).

[0003] Also disclosed is a method for producing a resist structure, which comprises treating an exposed photoresist layer with an aqueous or aqueous alcoholic solution of a polyfunctional amino or hydroxysiloxane and then etching in an oxygen-containing plasma (see Patent Document 2).

[0004] Furthermore, a pattern formation method has been disclosed in which a resist pattern is formed using a resist material containing a base generator, then a silicon-containing substance is coated to form crosslinked and uncrosslinked portions of the silicon-containing substance, and the uncrosslinked portions are then removed (see Patent Document 3).A hydroxyl-containing organic group is used as the silicon-containing substance.

[0005] Also disclosed is a pattern formation method in which an organic solvent of novolac resin or polyalkylsiloxane is used as a rinsing liquid or a subsequent coating liquid (see Patent Document 4).

[0006] A pattern formation method has been disclosed in which a rinsing liquid or a subsequent coating liquid uses an aqueous solvent of polyalkylsiloxane (see Patent Document 5). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent Publication No. 2005-277052 [Patent Document 2] Japanese Patent Application Publication No. 7-050286 [Patent Document 3] Patent Publication No. 2011-027980 [Patent Document 4] International Publication No. 2012 / 128251 Brochure [Patent Document 5] International Publication No. 2015 / 025665 Brochure Summary of the Invention [Problem to be solved by the invention]

[0008] dewA method in which the resist surface after exposure to light is developed with a developer, washed with a rinse solution, the rinse solution is replaced with a coating solution containing a polymer component, the resist pattern is coated with the polymer component, and then the resist is removed by dry etching, and a reverse pattern is formed with the replaced polymer component. but be. However, in the above method, when the resist is removed with a developer or rinse solution to form a resist pattern, Laplace forces are exerted, which may cause the pattern to collapse.

[0009] Furthermore, when resist patterns become fine, pattern collapse also occurs due to Laplace forces when the developer is spin-dried during development. The present invention provides a material and a method for preventing such pattern collapse.

[0010] More specifically, the present invention provides a material that can be used to reverse a pattern by gas etching by applying a polymer-containing coating composition onto a resist pattern to fill gaps between the patterns so as to prevent the resist pattern from collapsing when forming a fine pattern, and by drying forming a layer made of the polymer in the composition between the resist patterns, utilizing the difference in gas etching rate between the resist pattern and the polymer layer formed therebetween. [Means for solving the problem]

[0011] A first aspect of the present invention is a composition to be applied to a resist pattern, comprising the following component (A) and component (B): Component (A): at least one compound selected from the group consisting of a metal oxide (a1), a polyacid (a2), a polyacid salt (a3), a hydrolyzable silane (a4), a hydrolyzate of the hydrolyzable silane (a5), and a hydrolyzed condensate of the hydrolyzable silane (a6); (B) component: an aqueous solvent; The composition, wherein the hydrolyzable silane (a4) is a hydrolyzable silane (i) containing an organic group having an amino group, a hydrolyzable silane (ii) containing an organic group having an ionic functional group, a hydrolyzable silane (iii) containing an organic group having a hydroxyl group, or a hydrolyzable silane (iv) containing an organic group having a functional group that can be converted into a hydroxyl group; As a second aspect, the composition according to the first aspect, in which the metal oxide (a1) is an oxide of titanium, tungsten, zirconium, aluminum, or hafnium; As a third aspect, the composition according to the first aspect, wherein the polyacid (a2) is an isopolyacid selected from metatungstic acid and molybdic acid; As a fourth aspect, the composition according to the first aspect, in which the polyacid (a2) is a heteropolyacid selected from silicotungstic acid and phosphomolybdic acid; as a fifth aspect, the composition according to the first aspect, in which the polyacid salt (a3) ​​is an ammonium salt of the isopolyacid according to the third aspect or an ammonium salt of the heteropolyacid according to the fourth aspect; As a sixth aspect, the composition according to the first aspect, in which the hydrolyzable silane (a4) is hydrolyzed in the presence of an alkaline substance; As a seventh aspect, the composition according to the sixth aspect, wherein the alkaline substance is an alkaline catalyst added during hydrolysis of the hydrolyzable silane, or an amino group present inside the hydrolyzable silane molecule. As an eighth aspect, the composition according to the first aspect, wherein the hydrolyzate of the hydrolyzable silane (a4) is obtained by hydrolyzing the hydrolyzable silane (a4) in the presence of an acidic substance; As a ninth aspect, the hydrolyzable silane (a4) is represented by the formula (1) or the formula (1-1): [ka] (R in the formula 3 represents an organic group having an amino group, an organic group having an ionic functional group, an organic group having a hydroxyl group, or an organic group having a functional group that can be converted into a hydroxyl group by hydrolysis, and is bonded to a silicon atom via a Si-C bond or a Si-N bond, and R3 may form a ring and be bonded to the Si atom. 1 R represents an organic group having an alkyl group, an aryl group, a halogenated alkyl group, a halogenated aryl group, an alkenyl group, an epoxy group, an acryloyl group, a methacryloyl group, a mercapto group, or a cyano group, and is bonded to a silicon atom by a Si-C bond. 2 represents an alkoxy group, an acyloxy group, or a halogen group. a0 represents an integer of 0 or 1, b0 represents an integer of 1 to 3, and c0 represents an integer of 1 or 2. R 10 and R 20 each represents a hydroxyl group, an alkoxy group, an acyloxy group, or a halogen group, and R 30 represents an organic group having an amino group, an organic group having an ionic functional group, an organic group having a hydroxyl group, or an organic group having a functional group that can be converted into a hydroxyl group by hydrolysis, and is bonded to a silicon atom via a Si-C bond or a Si-N bond, and R 30 may form a ring and be bonded to the Si atom, and n0 represents an integer of 1 to 10. As a tenth aspect, the composition according to the first aspect is a composition comprising a hydrolyzable silane (a4) represented by formula (1) or formula (1-1) and a hydrolyzable silane (a5) represented by formula (2): [ka] (R in the formula 4 represents an organic group having an alkyl group, an aryl group, a halogenated alkyl group, a halogenated aryl group, an alkenyl group, an acryloyl group, a methacryloyl group, a mercapto group, or a cyano group, and is bonded to a silicon atom through a Si-C bond; R 5 represents an alkoxy group, an acyloxy group, or a halogen group, and a represents an integer of 0 to 3. [ka] (R in the formula 6 represents an alkyl group, and R 7represents an alkoxy group, an acyloxy group, or a halogen group, Z represents an alkylene group or an arylene group, b represents an integer of 0 or 1, and c represents an integer of 0 or 1. As an eleventh aspect, the composition according to the tenth aspect, wherein the hydrolyzable silane comprises a hydrolyzable silane (a4) and a hydrolyzable silane (b) in a molar ratio of (a4):(b)=3:97 to 100:0; As a twelfth aspect, the composition according to the first aspect, in which the hydrolyzed condensate (a6) of the hydrolyzable silane is a random-type, ladder-type, or cage-type silsesquioxane; As a thirteenth aspect, the composition according to any one of the first to twelfth aspects, further comprising an acid or a base; as a fourteenth aspect, the composition according to any one of the first to thirteenth aspects, further comprising a surfactant; as a fifteenth aspect, the composition according to any one of the first to fourteenth aspects, further comprising a photoacid generator; as a sixteenth aspect, a method for producing a semiconductor device, comprising: a step (1) of applying a resist onto a substrate; a step (2) of exposing and developing the resist; a step (3) of applying the composition according to any one of the first to fifteenth aspects to the resist pattern during or after development; and a step (4) of etching away the resist pattern to reverse the pattern; As a seventeenth aspect, the production method according to the sixteenth aspect, including, before the step (1), a step (1-1) of forming a resist underlayer film on a substrate; As an eighteenth aspect, the production method according to the sixteenth or seventeenth aspect, further comprising a step (3-1) of etching back a surface of the coating film formed after the step (3) to expose a surface of the resist pattern; and As a 19th aspect, there is provided a method for manufacturing a semiconductor device, comprising: a step (a) of forming a resist underlayer film on a substrate; a step (b) of forming a hard mask thereon; a step (c) of forming a resist film thereon; a step (d) of forming a resist pattern by exposure to light or an electron beam and development; a step (e) of etching the hard mask using the resist pattern; a step (f) of etching the resist underlayer film using the patterned hard mask; a step (g) of applying a composition according to any of the first to fifteenth aspects to the patterned resist underlayer film; and a step (h) of etching away the resist underlayer film to invert the pattern. The present invention also relates to a composition which contains the following components (A) and (B) and is applied to a resist pattern to reverse the pattern by utilizing a difference in gas etching rate, the component (A) being at least one compound selected from the group consisting of polyacid (a2), polyacid salt (a3), hydrolyzable silane (a4), hydrolysate (a5) of the hydrolyzable silane, and hydrolyzed condensate (a6) of the hydrolyzable silane; the component (B) being an aqueous solvent, the hydrolyzable silane (a4) being a hydrolyzable silane containing an organic group having a tertiary amino group; the composition comprising (i) a hydrolyzable silane containing an organic group having an ionic functional group (ii) or (iii) a hydrolyzable silane containing an organic group having a hydroxyl group, the polyacid (a2) being an isopolyacid consisting of molybdic acid, or a heteropolyacid selected from silicotungstic acid and phosphomolybdic acid, and the polyacid salt (a3) ​​being an ammonium salt of an isopolyacid consisting of molybdic acid, or an ammonium salt of a heteropolyacid selected from silicotungstic acid and phosphomolybdic acid, A method for producing a semiconductor device, comprising: a step (1) of applying a resist onto a substrate; a step (2) of exposing and developing the resist; a step (3) of applying the composition to the resist pattern during or after development; and a step (4) of removing the resist pattern by gas etching to reverse the pattern; The present invention relates to a method for manufacturing a semiconductor device, comprising the steps of: (a) forming a resist underlayer film on a substrate; (b) forming a hard mask thereon; (c) forming a resist film thereon; (d) forming a resist pattern by exposure to light or an electron beam and development; (e) etching the hard mask using the resist pattern; (f) etching the resist underlayer film using the patterned hard mask; (g) applying the composition to the patterned resist underlayer film; and (h) removing the resist underlayer film by gas etching to invert the pattern. The present invention also provides a composition which contains the following components (A) and (B), and which is applied to a resist pattern to reverse the pattern by utilizing a difference in gas etching rates: Component (A): at least one compound selected from the group consisting of hydrolyzable silanes (a4), hydrolysates of the above hydrolyzable silanes (a5), and hydrolyzed condensates of the above hydrolyzable silanes (a6); (B) component: aqueous solvent, The hydrolyzable silane (a4) includes a hydrolyzable silane (i) containing an organic group having a tertiary amino group, a hydrolyzable silane (ii) containing an organic group having an ionic functional group, or a hydrolyzable silane (iii) containing an organic group having a hydroxyl group; The hydrolyzate of the hydrolyzable silane (a4) is obtained by hydrolyzing the hydrolyzable silane (a4) in the presence of an alkaline substance or an acidic substance, A method for producing a semiconductor device, comprising: a step (1) of applying a resist onto a substrate; a step (2) of exposing and developing the resist; a step (3) of applying the composition to the resist pattern during or after development; and a step (4) of removing the resist pattern by gas etching to reverse the pattern; The present invention relates to a method for manufacturing a semiconductor device, comprising the steps of: (a) forming a resist underlayer film on a substrate; (b) forming a hard mask thereon; (c) forming a resist film thereon; (d) forming a resist pattern by exposure to light or an electron beam and development; (e) etching the hard mask using the resist pattern; (f) etching the resist underlayer film using the patterned hard mask; (g) applying the composition to the patterned resist underlayer film; and (h) removing the resist underlayer film by gas etching to invert the pattern. Effect of the Invention

[0012] The coating composition containing the pattern-forming polymer of the present invention is brought into contact with the resist surface during or after development of the resist after mask exposure, and the gaps between the resist patterns are filled with the polymer, thereby preventing the resist pattern from collapsing. The surface in which the gaps between the resist patterns are filled with the polymer is then dry etched, and the resist pattern is removed, whereby the filled polymer becomes a new resist pattern. The present invention is capable of forming a fine pattern that does not collapse by this reverse process.

[0013] When the coating composition that has been applied to and filled in the resist pattern completely covers the resist pattern, it can be etched back by dry etching to expose the resist surface, and then dry etched with a gas (oxygen-based gas) that has a high resist etching rate to reverse the pattern. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention provides a composition to be applied to a resist pattern, comprising the following components (A) and (B): Component (A): at least one compound selected from the group consisting of a metal oxide (a1), a polyacid (a2), a polyacid salt (a3), a hydrolyzable silane (a4), a hydrolyzate of the hydrolyzable silane (a5), and a hydrolyzed condensate of the hydrolyzable silane (a6); (B) component: an aqueous solvent; The composition, wherein the hydrolyzable silane (a4) is a hydrolyzable silane (i) containing an organic group having an amino group, a hydrolyzable silane (ii) containing an organic group having an ionic functional group, a hydrolyzable silane (iii) containing an organic group having a hydroxyl group, or a hydrolyzable silane (iv) containing an organic group having a functional group convertible to a hydroxyl group.

[0015] The composition is a solvent in which at least one compound selected from the group consisting of metal oxide (a1), polyacid (a2), polyacid salt (a3), hydrolyzable silane (a4), hydrolyzate of the hydrolyzable silane (a5), and hydrolyzed condensate of the hydrolyzable silane (a6) is dissolved, and the solid content is 0.5 to 20.0 mass %, or 1.0 to 10.0 mass %. The solid content is the percentage of the remainder after removing the solvent from the composition. The above (a6) is polysiloxane. The proportion of at least one compound selected from the group consisting of the metal oxide (a1), the polyacid (a2), the polyacid salt (a3), the hydrolyzable silane (a4), the hydrolyzate of the hydrolyzable silane (a5), and the hydrolyzed condensate of the hydrolyzable silane (a6) in the solid content is 50 to 100 mass %, or 80 to 100 mass %. The metal oxide (a1), polyacid (a2), polyacid salt (a3), hydrolysis The concentration of at least one compound selected from the group consisting of the hydrolyzable silane (a4), the hydrolyzate of the hydrolyzable silane (a5), and the hydrolyzed condensate of the hydrolyzable silane (a6) is 0.5 to 20.0 mass %. In the case where the component (A) is classified into a component (A1) selected from metal oxides (a1), polyacids (a2), and polyacid salts (a3), and a component (A2) selected from hydrolyzable silanes (a4), hydrolyzates of the hydrolyzable silanes (a5), and hydrolyzed condensates of the hydrolyzable silanes (a6), the component (A1) may be used alone, the component (A2) may be used alone, or the components (A1) and (A2) may be mixed together. When the components (A1) and (A2) are mixed together, the ratio of the components (A1):(A2) may be 50:1 to 0.05:1 by mass.

[0016] Since the present invention is a coating composition used after exposure of the resist, following exposure of the resist through a mask, the composition is filled onto the resist pattern during or after development.

[0017] The above hydrolyzable silane, its hydrolysate, and its hydrolysis condensate have a resin component different from that of the resist. As a result, in the subsequent dry etching process, the resist is selectively removed by dry etching by selecting the type of gas, and a new pattern is formed by the filled hydrolysis condensation product (polysiloxane) or inorganic compound.

[0018] The solvent used in the composition is preferably water, and preferably the solvent is 100% water, that is, the solvent is only water. This is because the composition is applied to the resist pattern, and therefore a solvent that may dissolve the resist pattern cannot be used. However, the composition may contain a water-soluble organic solvent that is miscible with the water solvent and does not dissolve the resist pattern, such as an alcohol-based solvent or an ether-based solvent.

[0019] The above-mentioned hydrolyzable silane, its hydrolyzate, and its hydrolysis condensate can also be used as a mixture thereof. Also, a condensate obtained by hydrolyzing the hydrolyzable silane and condensing the obtained hydrolyzate can be used. A partial hydrolyzate in which hydrolysis is not completely completed when obtaining a hydrolysis condensate, or a silane compound can be mixed with the hydrolysis condensate, and the mixture can be used. This condensate is a polymer having a polysiloxane structure.

[0020] At least one compound selected from the group consisting of metal oxides (a1), polyacids (a2), polyacid salts (a3), hydrolyzable silanes (a4), hydrolysates of the hydrolyzable silanes (a5), and hydrolyzed condensates of the hydrolyzable silanes (a6) can be contained in an amount of 0.001 to 100 parts by mass per 100 parts by mass of the composition to be applied to the resist pattern.

[0021] The metal oxide (a1) may be selected from the oxides of titanium, tungsten, zirconium, aluminum, or hafnium.

[0022] The polyacid (a2) may be an isopolyacid selected from metatungstic acid or molybdic acid.

[0023] The polyacid (a2) may be a heteropolyacid selected from silicotungstic acid and phosphomolybdic acid.

[0024] The polyacid salt (a3) ​​can be an ammonium salt of the above-mentioned isopolyacid or heteropolyacid.

[0025] The above metal oxides can also be used as partial metal oxides. Examples of the metal oxides include hydrolysis condensates containing TiOx (titanium oxide, x=1 to 2), hydrolysis condensates containing WOx (tungsten oxide, x=1 to 3), hydrolysis condensates containing HfOx (hafnium oxide, x=1 to 2), hydrolysis condensates containing ZrOx (zirconium oxide, x=1 to 2), hydrolysis condensates containing AlOx (aluminum oxide, x=1 to 1.5), metatungstic acid, ammonium metatungstate, silicotungstic acid, ammonium silicotungstate, molybdic acid, ammonium molybdate, phosphomolybdic acid, and ammonium phosphomolybdate. The amount of the metal oxide to be added can be 0.001 to 100 parts by mass relative to 100 parts by mass of the composition to be applied to the resist pattern. The metal oxide or partial metal oxide can be obtained as a hydrolysis condensate of a metal alkoxide, and the partial metal oxide may contain an alkoxide group.

[0026] The hydrolyzable silane (a4) can be a hydrolyzable silane represented by formula (1) or formula (1-1). The hydrolyzate (a5) of the hydrolyzable silane corresponds to the hydrolyzate of the hydrolyzable silane (a4). The hydrolyzed condensate (a6) of the hydrolyzable silane corresponds to the condensate of the hydrolyzate (a5) of the hydrolyzable silane (a4). In formula (1), R 3 represents an organic group having an amino group, an organic group having an ionic functional group, an organic group having a hydroxyl group, or an organic group having a functional group that can be converted into a hydroxyl group by hydrolysis, which is bonded to a silicon atom via a Si-C bond or a Si-N bond, and R 3 may form a ring and be bonded to the Si atom. 1 R represents an organic group having an alkyl group, an aryl group, a halogenated alkyl group, a halogenated aryl group, an alkenyl group, an epoxy group, an acryloyl group, a methacryloyl group, a mercapto group, or a cyano group, and is bonded to a silicon atom by a Si-C bond. 2represents an alkoxy group, an acyloxy group, or a halogen group. a0 represents an integer of 0 or 1, b0 represents an integer of 1 to 3, and c0 represents an integer of 1 or 2. In formula (1-1), R 10 and R 20 each represents a hydroxyl group, an alkoxy group, an acyloxy group, or a halogen group, and R 30 represents an organic group having an amino group, an organic group having an ionic functional group, an organic group having a hydroxyl group, or an organic group having a functional group that can be converted into a hydroxyl group by hydrolysis, and is bonded to a silicon atom via a Si-C bond or a Si-N bond, and R 30 may form a ring and be bonded to the Si atom. n0 can be an integer of 1 to 10, or an integer of 1 to 5, or an integer of 1.

[0027] R in formula (1) 3 Or R in formula (1-1) 30 Examples of the amino group include organic groups having an amino group. As the amino group, a primary amino group, a secondary amino group, or a tertiary amino group can be used, and the molecule can have one amino group or multiple amino groups (2 or 3). These can include an aliphatic amino group, an aromatic amino group, etc. In addition, R in formula (1) 3 Or R in formula (1-1) 30 Examples of the ionic functional group include an organic group having an ionic functional group. Examples of the ionic functional group include an ammonium cation, a carboxylate anion, a sulfonate anion, a nitrate anion, a phosphate anion, a sulfonium anion, and an alcoholate anion. Examples of the ammonium cation include primary ammonium, secondary ammonium, tertiary ammonium, and quaternary ammonium.

[0028] The counter ions of the ionic functional groups are, as anions, chloride anion, fluoride anion, bromide anion, iodide anion, nitrate anion, sulfate anion, phosphate anion, formate anion, acetate anion, propionate anion, maleate anion, oxalate anion, malonate anion, methylmalonate anion, succinate anion, malate anion, tartrate anion, phthalate anion, citrate anion, glutarate anion, citrate anion, lactate anion, salicylate anion, methanesulfonate anion, Examples of the anion include an anion of octanoic acid, an anion of decanoic acid, an anion of octanesulfonic acid, an anion of decane sulfonic acid, an anion of dodecylbenzenesulfonic acid, an anion of phenolsulfonic acid, an anion of sulfosalicylic acid, an anion of camphorsulfonic acid, an anion of nonafluorobutanesulfonic acid, an anion of toluenesulfonic acid, an anion of cumenesulfonic acid, an anion of p-octylbenzenesulfonic acid, an anion of p-decylbenzenesulfonic acid, an anion of 4-octyl 2-phenoxybenzenesulfonic acid, an anion of 4-carboxybenzenesulfonic acid, etc. Also, the unit structure of a silane having an anionic functional group, a polysiloxane having an anionic functional group, or a polysiloxane having an anionic functional group for forming an intramolecular salt may be used. The counter ion of the ionic functional group may be a cation, such as a hydrogen cation, an ammonium cation, a sulfonium cation, an iodonium cation, a phosphonium cation, or an oxonium cation.

[0029] In addition, R in formula (1) 3 Or R in formula (1-1) 30 Examples of the organic group include an organic group having a hydroxyl group or an organic group having a functional group that can be converted into a hydroxyl group by hydrolysis. In the organic group having a hydroxyl group or an organic group having a functional group that can be converted to a hydroxyl group by hydrolysis, examples of the organic group include an alkyl group, an aryl group, etc., which may contain an ether bond or an amino group. Examples of organic groups having a functional group that can be converted into a hydroxyl group include organic groups having an acyloxy group such as an acetoxy group, an epoxy group such as a glycidyl group, an alkoxy group such as a methoxy group, an ethoxy group, a propoxy group, or a butoxy group, and a halogen group such as a fluorine group, a chloro group, a bromo group, or an iodo group.

[0030] The alkyl group mentioned above is a straight-chain or branched alkyl group having 1 to 10 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, an i-butyl group, an s-butyl group, a t-butyl group, an n-pentyl group, a 1-methyl-n-butyl group, a 2-methyl-n-butyl group, a 3-methyl-n-butyl group, a 1,1-dimethyl-n-propyl group, a 1,2-dimethyl-n-propyl group, a 2,2-dimethyl-n-propyl group, a 1-ethyl-n-propyl group, an n-hexyl group, a 1-methyl-n-pentyl group, a 2-methyl-n- Examples of such alkyl groups include pentyl, 3-methyl-n-pentyl, 4-methyl-n-pentyl, 1,1-dimethyl-n-butyl, 1,2-dimethyl-n-butyl, 1,3-dimethyl-n-butyl, 2,2-dimethyl-n-butyl, 2,3-dimethyl-n-butyl, 3,3-dimethyl-n-butyl, 1-ethyl-n-butyl, 2-ethyl-n-butyl, 1,1,2-trimethyl-n-propyl, 1,2,2-trimethyl-n-propyl, 1-ethyl-1-methyl-n-propyl and 1-ethyl-2-methyl-n-propyl groups.

[0031] Cyclic alkyl groups can also be used. Examples of cyclic alkyl groups having 1 to 10 carbon atoms include cyclopropyl, cyclobutyl, 1-methylcyclopropyl, 2-methylcyclopropyl, cyclopentyl, 1-methylcyclobutyl, 2-methylcyclobutyl, 3-methylcyclobutyl, 1,2-dimethylcyclopropyl, 2,3-dimethylcyclopropyl, 1-ethylcyclopropyl, 2-ethylcyclopropyl, cyclohexyl, 1-methylcyclopentyl ...propyl, 3-methylcyclopropyl, 3-methylcyclopropyl, 3-methylcyclopropyl, 3-methylcyclopropyl, 3-methylcyclopropyl, 3-methylcyclopropyl, 3-methylcyclopropyl, 3-methylcyclopropyl, 3-methylcyclopropyl, 3-methylcyclopropyl, 3-methylcyclopropyl, 3-methylcyclopropyl, 3-methylcyclopropyl, 3-methylcyclopropyl, 3-methylcyclopropyl, 3 Cyclopentyl, 3-methylcyclopentyl, 1-ethylcyclobutyl, 2-ethylcyclobutyl, 3-ethylcyclobutyl, 1,2-dimethylcyclobutyl, 1,3-dimethylcyclobutyl, 2,2-dimethylcyclobutyl, 2,3-dimethylcyclobutyl, 2,4-dimethylcyclobutyl, 3,3-dimethylcyclobutyl, 1-n-propylcyclopropyl, 2-n-propylcyclopropyl, 1-i-propylcyclopropyl, 2-i-propylcyclopropyl, Examples of such cycloalkyl groups include a 1,2,2-trimethyl-cyclopropyl group, a 1,2,3-trimethyl-cyclopropyl group, a 2,2,3-trimethyl-cyclopropyl group, a 1-ethyl-2-methyl-cyclopropyl group, a 2-ethyl-1-methyl-cyclopropyl group, a 2-ethyl-2-methyl-cyclopropyl group, and a 2-ethyl-3-methyl-cyclopropyl group.

[0032] The aryl group mentioned above includes aryl groups having 6 to 20 carbon atoms, such as a phenyl group, an o-methylphenyl group, a m-methylphenyl group, a p-methylphenyl group, an o-chlorophenyl group, a m-chlorophenyl group, a p-chlorophenyl group, an o-fluorophenyl group, a p-mercaptophenyl group, an o-methoxyphenyl group, a p-methoxyphenyl group, a p-aminophenyl group, a p-cyanophenyl group, an α-naphthyl group, a β-naphthyl group, an o-biphenylyl group, a m-biphenylyl group, a p-biphenylyl group, a 1-anthryl group, a 2-anthryl group, a 9-anthryl group, a 1-phenanthryl group, a 2-phenanthryl group, a 3-phenanthryl group, a 4-phenanthryl group, and a 9-phenanthryl group. The above-mentioned halogenated alkyl groups and halogenated aryl groups include the above-mentioned alkyl and aryl groups in which a hydrogen atom has been substituted with a halogen atom such as fluorine, chlorine, bromine or iodine.

[0033] The above-mentioned alkenyl group is an alkenyl group having 2 to 10 carbon atoms, and examples thereof include ethenyl group, 1-propenyl group, 2-propenyl group, 1-methyl-1-ethenyl group, 1-butenyl group, 2-butenyl group, 3-butenyl group, 2-methyl-1-propenyl group, 2-methyl-2-propenyl group, 1-ethylethenyl group, 1-methyl-1-propenyl group, 1-methyl-2-propenyl group, 1-pentenyl group, 2-pentenyl group, 3-pentenyl group, 4-pentenyl group, 1-n-propylethenyl group, 1-methyl-1-butenyl group, 1-methyl-2-butenyl group, 1- Methyl-3-butenyl, 2-ethyl-2-propenyl, 2-methyl-1-butenyl, 2-methyl-2-butenyl, 2-methyl-3-butenyl, 3-methyl-1-butenyl, 3-methyl-2-butenyl, 3-methyl-3-butenyl, 1,1-dimethyl-2-propenyl, 1-i-propylethenyl, 1,2-dimethyl-1-propenyl, 1,2-dimethyl-2-propenyl, 1-cyclopentenyl, 2-cyclopentenyl, 3-cyclopentenyl, 1-hexenyl, 2-hexenyl, 3-hexenyl, 4-hexenyl group, 5-hexenyl group, 1-methyl-1-pentenyl group, 1-methyl-2-pentenyl group, 1-methyl-3-pentenyl group, 1-methyl-4-pentenyl group, 1-n-butylethenyl group, 2-methyl-1-pentenyl group, 2-methyl-2-pentenyl group, 2-methyl-3-pentenyl group, 2-methyl-4-pentenyl group, 2-n-propyl-2-propenyl group, 3-methyl-1-pentenyl group, 3-methyl-2-pentenyl group, 3-methyl-3-pentenyl group, 3-methyl-4-pentenyl group, 3-ethyl-3-butenyl group, 4-methyl-1-pentenyl group group, 4-methyl-2-pentenyl group, 4-methyl-3-pentenyl group, 4-methyl-4-pentenyl group, 1,1-dimethyl-2-butenyl group, 1,1-dimethyl-3-butenyl group, 1,2-dimethyl-1-butenyl group, 1,2-dimethyl-2-butenyl group, 1,2-dimethyl-3-butenyl group, 1-methyl-2-ethyl-2-propenyl group, 1-s-butylethenyl group, 1,3-dimethyl-1-butenyl group, 1,3-dimethyl-2-butenyl group, 1,3-dimethyl-3-butenyl group, 1-i-butylethenyl group, 2,2-dimethyl-3-butenyl group, 2,3-dimethyl-1-butenyl group, 2,3-dimethyl-2-butenyl group, 2,3-dimethyl-3-butenyl group, 2-i-propyl-2-propenyl group, 3,3-dimethyl-1-butenyl group, 1-ethyl-1-butenyl group, 1-ethyl-2-butenyl group, 1-ethyl-3-butenyl group, 1-n-propyl-1-propenyl group, 1-n-propyl-2-propenyl group, 2-ethyl-1-butenyl group, 2-ethyl-2-butenyl group, 2-ethyl-3-butenyl group, 1,1,2-trimethyl-2-propenyl group, 1-t-butylethenyl group, 1-methyl-1-ethyl-2-propenyl group, 1-ethyl-2-methyl-1-propenyl group, 1-ethyl-2-methyl-2-propenyl group, 1-i-propyl-1-propenyl group, 1-i-, Examples of such aryl groups include propyl-2-propenyl group, 1-methyl-2-cyclopentenyl group, 1-methyl-3-cyclopentenyl group, 2-methyl-1-cyclopentenyl group, 2-methyl-2-cyclopentenyl group, 2-methyl-3-cyclopentenyl group, 2-methyl-4-cyclopentenyl group, 2-methyl-5-cyclopentenyl group, 2-methylene-cyclopentyl group, 3-methyl-1-cyclopentenyl group, 3-methyl-2-cyclopentenyl group, 3-methyl-3-cyclopentenyl group, 3-methyl-4-cyclopentenyl group, 3-methyl-5-cyclopentenyl group, 3-methylene-cyclopentyl group, 1-cyclohexenyl group, 2-cyclohexenyl group, and 3-cyclohexenyl group. Further, examples of the organic groups include those substituted with halogen atoms such as fluorine, chlorine, bromine, or iodine.

[0034] Examples of the organic group having an epoxy group include glycidoxymethyl, glycidoxyethyl, glycidoxypropyl, glycidoxybutyl, and epoxycyclohexyl groups. Examples of the organic group having an acryloyl group include an acryloylmethyl group, an acryloylethyl group, and an acryloylpropyl group. Examples of the organic group having a methacryloyl group include methacryloylmethyl, methacryloylethyl, and methacryloylpropyl groups. Examples of the organic group having a mercapto group include an ethyl mercapto group, a butyl mercapto group, a hexyl mercapto group, and an octyl mercapto group. Examples of the organic group having a cyano group include a cyanoethyl group and a cyanopropyl group.

[0035] R in the above formula (1) 2 , R in formula (1-1) 10 and R 20 , R in Eq. (2) 5 , R in Equation (3) 7In the above formula, examples of the alkoxy group include alkoxy groups having a straight-chain, branched or cyclic alkyl moiety having 1 to 20 carbon atoms, such as a methoxy group, an ethoxy group, an n-propoxy group, an i-propoxy group, an n-butoxy group, an i-butoxy group, an s-butoxy group, a t-butoxy group, an n-pentyloxy group, a 1-methyl-n-butoxy group, a 2-methyl-n-butoxy group, a 3-methyl-n-butoxy group, a 1,1-dimethyl-n-propoxy group, a 1,2-dimethyl-n-propoxy group, a 2,2-dimethyl-n-propoxy group, a 1-ethyl-n-butoxy group, a 2-ethyl-n-butoxy group, a 2-ethyl-n-prop ... n-propoxy, n-hexyloxy, 1-methyl-n-pentyloxy, 2-methyl-n-pentyloxy, 3-methyl-n-pentyloxy, 4-methyl-n-pentyloxy, 1,1-dimethyl-n-butoxy, 1,2-dimethyl-n-butoxy, 1,3-dimethyl-n-butoxy, 2,2-dimethyl-n-butoxy, 2,3-dimethyl-n-butoxy, 3,3-dimethyl-n-butoxy, 1-ethyl-n-butoxy, 2-ethyl-n-butoxy, 1,1,2-trimethyl-n-propoxy, Examples of cyclic alkoxy groups include cyclopropoxy, cyclobutoxy, 1-methyl-cyclopropoxy, 2-methyl-cyclopropoxy, cyclopentyloxy, 1-methyl-cyclobutoxy, 2-methyl-cyclobutoxy, 3-methyl-cyclobutoxy, 1,2-dimethyl-cyclopropoxy, 2,3-dimethyl-cyclopropoxy, 1-ethyl-cyclopropoxy, 2-ethyl-cyclopropoxy, cyclohexyloxy, 1-methyl-cyclopentyloxy, 2-methyl-cyclopentyloxy, 3-methyl-cyclopentyloxy, 1-ethyl-cyclobutoxy, 2-ethyl-cyclobutoxy, 3-ethyl-cyclobutoxy, 1,2-dimethyl-cyclobutoxy, 1,3-dimethyl-cyclobutoxy, 2,2-dimethyl-cyclobutoxy, 2,3-dimethyl-cyclobutoxy, 2,4-dimethyl-cyclobutoxy, 3,3-Dimethyl-cyclobutoxy group, 1-n-propyl-cyclopropoxy group, 2-n-propyl-cyclopropoxy group, 1-i-propyl-cyclopropoxy group, 2-i-propyl-cyclopropoxy group, 1,2,2-trimethyl-cyclopropoxy group, Examples of such cyclopropoxy groups include a 1,2,3-trimethyl-cyclopropoxy group, a 2,2,3-trimethyl-cyclopropoxy group, a 1-ethyl-2-methyl-cyclopropoxy group, a 2-ethyl-1-methyl-cyclopropoxy group, a 2-ethyl-2-methyl-cyclopropoxy group, and a 2-ethyl-3-methyl-cyclopropoxy group.

[0036] R in the above formula (1) 2 , R in formula (1-1) 10 and R 20 , R in Eq. (2) 5 , R in Equation (3) 7The acyloxy group in the formula (I) is an acyloxy group having 1 to 20 carbon atoms, and examples of the acyloxy group include a methylcarbonyloxy group, an ethylcarbonyloxy group, an n-propylcarbonyloxy group, an i-propylcarbonyloxy group, an n-butylcarbonyloxy group, an i-butylcarbonyloxy group, an s-butylcarbonyloxy group, a t-butylcarbonyloxy group, an n-pentylcarbonyloxy group, a 1-methyl-n-butylcarbonyloxy group, a 2-methyl-n-butylcarbonyloxy group, a 3-methyl-n-butylcarbonyloxy group, a 1,1-dimethyl-n-propylcarbonyloxy group, a 1,2-dimethyl-n-propylcarbonyloxy group, a 2,2-dimethyl-n-propylcarbonyloxy group, a 1-ethyl-n-propylcarbonyloxy group, an n-hexylcarbonyloxy group, a 1-methyl-n-pentylcarbonyloxy group, a 2-methyl-n-pentylcarbonyloxy group, nyloxy group, 3-methyl-n-pentylcarbonyloxy group, 4-methyl-n-pentylcarbonyloxy group, 1,1-dimethyl-n-butylcarbonyloxy group, 1,2-dimethyl-n-butylcarbonyloxy group, 1,3-dimethyl-n-butylcarbonyloxy group, 2,2-dimethyl-n-butylcarbonyloxy group, 2,3-dimethyl-n-butylcarbonyloxy group, 3,3-dimethyl-n-butylcarbonyloxy group, 1-ethyl-n-butylcarbonyloxy group, 2-ethyl-n-butylcarbonyloxy group, 1,1,2-trimethyl-n-propylcarbonyloxy group, 1,2,2-trimethyl-n-propylcarbonyloxy group, 1-ethyl-1-methyl-n-propylcarbonyloxy group, 1-ethyl-2-methyl-n-propylcarbonyloxy group, phenylcarbonyloxy group, and tosylcarbonyloxy group. R in the above formula (1) 2 , R in formula (1-1) 10 and R 20 , R in Eq. (2) 5 , R in Equation (3) 7 Examples of the halogen group in include fluorine, chlorine, bromine, and iodine.

[0037] The alkylene group or arylene group in Z may be a divalent organic group derived from the alkyl group or aryl group described above.

[0038] In the hydrolyzable silane represented by formula (1), R 3 Examples of compounds containing an organic group having an amino group are shown below. In the following exemplary compounds, T represents a hydrolyzable group, such as an alkoxy group, an acyloxy group, or a halogen group, and specific examples of these groups include the above-mentioned examples. In particular, alkoxy groups such as a methoxy group and an ethoxy group are preferred.

[0039] [ka] [ka] [ka]

[0040] [ka] [ka] [ka]

[0041] [ka] [ka] [ka]

[0042] [ka] [ka]

change

[0043]

change

change

change

[0044]

change

change

change

[0045]

change

change

change

[0046]

change

change

change

[0047]

change

[0048] [ka] [ka] [ka]

[0049] [ka] [ka] [ka]

[0050] [ka] [ka] [ka]

[0051] In the hydrolyzable silane represented by formula (1), R 3 Examples of hydrolyzable silanes represented by the formula (1-1), in which R 30Examples of compounds containing an organic group having an ionic functional group are given below. In the following example compounds, T represents a hydrolyzable group, and represents an alkoxy group, an acyloxy group, or a halogen group, and examples thereof include those mentioned above. In particular, alkoxy groups such as methoxy and ethoxy groups are preferred. X and Y in the following formulas represent counter ions of the ionic functional group, and specific examples include anions and cations as counter ions of the ionic functional group mentioned above. In the formulas, X - , Y + are shown as monovalent anions and monovalent cations, respectively, but X - , Y + If the above ion examples indicate a divalent ion, the coefficient in front of the ion designation is multiplied by 1 / 2, and if the above examples indicate a trivalent ion, the coefficient in front of the ion designation is multiplied by 1 / 3.

[0052] [ka] [ka] [ka] [ka]

[0053] [ka] [ka] [ka]

[0054] [ka] [ka]

change

[0055]

change

change

change

[0056]

change

change

change

[0057]

change

change

change

[0058]

change

change

change

[0059]

change

change

change

[0060]

change

change

change

[0061]

change

change

change

[0062]

change

change

change

[0063]

change

change

change

[0064]

change

[0065] [ka] [ka]

[0066] In the hydrolyzable silane represented by formula (1), R 3 In the hydrolyzable silane represented by formula (1-1), R 30 However, examples of organic groups having a hydroxyl group or organic groups having a functional group that can be converted to a hydroxyl group by hydrolysis are given below. In the following example compounds, T represents a hydrolyzable group, and represents an alkoxy group, an acyloxy group, or a halogen group, and examples of these include the above-mentioned examples. In particular, alkoxy groups such as methoxy and ethoxy groups are preferred.

[0067] [ka] [ka] [ka]

[0068] [ka] [ka] [ka] [ka] [ka]

[0069] In the above formula, n1 represents an integer of 1 to 12, n2 represents an integer of 1 to 12, and n3 represents an integer of 5 to 8.

[0070] The hydrolyzable silane (a4) in the composition of the present invention can be a combination of the hydrolyzable silane (a4) represented by formula (1) or formula (1-1) and another hydrolyzable silane (b). The hydrolyzable silane (b) used in the present invention is a hydrolyzable silane represented by formula (2) or formula (3), and at least one organosilicon compound selected from the group consisting of the hydrolyzable silanes represented by formula (2) and formula (3) can be used.

[0071] Among the hydrolyzable silanes (b) selected from the group consisting of hydrolyzable silanes represented by formula (2) and formula (3), it is preferable to use the hydrolyzable silane represented by formula (2). The hydrolyzable silane may be a hydrolyzable silane containing the hydrolyzable silane (a4) and the hydrolyzable silane (b) in a molar ratio of (a4):(b)=3:97 to 100 to 0, or 30:70 to 100:0, or 50:50 to 100:0, or 70:30 to 100:0, or 97:3 to 100:0.

[0072] In formula (2), R 4 is an organic group having an alkyl group, an aryl group, a halogenated alkyl group, a halogenated aryl group, an alkenyl group, an acryloyl group, a methacryloyl group, a mercapto group, or a cyano group, and is bonded to a silicon atom by a Si-C bond; R 5 represents an alkoxy group, an acyloxy group, or a halogen group, and a represents an integer of 0 to 3.

[0073] In addition, in formula (3), R 6 represents an alkyl group, and R 7represents an alkoxy group, an acyloxy group, or a halogen group; Z represents an alkylene group or an arylene group; b represents an integer of 0 or 1; and c represents an integer of 0 or 1. Specific examples of these groups include those mentioned above.

[0074] Examples of the hydrolyzable silane represented by formula (2) include tetramethoxysilane, tetrachlorosilane, tetraacetoxysilane, tetraethoxysilane, tetra-n-propoxysilane, tetraisopropoxysilane, tetra-n-butoxysilane, tetraacetoxysilane, methyltrimethoxysilane, methyltriethoxysilane, methyltrichlorosilane, methyltriacetoxysilane, methyltrippropoxysilane, methyltriacetylsilane, methyltributoxysilane, methyltrippropoxysilane, methyltriamyloxysilane, methyltriphenoxysilane, methyltribenzyloxysilane, methyltriphenethyloxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, vinyltrimethoxysilane, vinyltrichlorosilane, vinyltriacetoxysilane, vinyltriethoxysilane, vinyl Examples of the silane include triacetoxysilane, phenyltrimethoxysilane, phenyltrichlorosilane, phenyltriacetoxysilane, phenyltriethoxysilane, phenyltriacetoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, β-cyanoethyltriethoxysilane, dimethyldimethoxysilane, phenylmethyldimethoxysilane, dimethyldiethoxysilane, phenylmethyldiethoxysilane, dimethyldiacetoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-mercaptopropylmethyldimethoxysilane, γ-mercaptomethyldiethoxysilane, methylvinyldimethoxysilane, and methylvinyldiethoxysilane.

[0075] Examples of hydrolyzable silanes represented by formula (3) include methylene bistrimethoxysilane, methylene bistrichlorosilane, methylene bistriacetoxysilane, ethylene bistriethoxysilane, ethylene bistrichlorosilane, ethylene bistriacetoxysilane, propylene bistriethoxysilane, butylene bistrimethoxysilane, phenylene bistrimethoxysilane, phenylene bistriethoxysilane, phenylene bismethyldiethoxysilane, phenylene bismethyldimethoxysilane, naphthylene bistrimethoxysilane, bistrimethoxydisilane, bistriethoxydisilane, bisethyldiethoxydisilane, and bismethyldimethoxydisilane.

[0076] Examples of the hydrolysis condensation product that can be used in the present invention are shown below. [ka] [ka] [ka]

[0077] [ka] [ka] [ka] In the above formula (2-3-3), n4 represents an integer of 8 to 12.

[0078] [ka] [ka]

[0079] [ka] [ka]

[0080] Examples of silsesquioxane (also called polysilsesquioxane) type polysiloxanes include those represented by formulae (2-1-4), (2-2-4), and (2-3-4). Formula (2-1-4) represents a ladder-type silsesquioxane, and n represents 1 to 1000, or 1 to 200. Formula (2-2-4) represents a cage-type silsesquioxane. Formula (2-3-4) represents a random-type silsesquioxane. In formulas (2-1-4), (2-2-4), and (2-3-4), R represents an organic group having an amino group, an organic group having an ionic functional group, an organic group having a hydroxyl group, or an organic group having a functional group that can be converted to a hydroxyl group by hydrolysis, and is bonded to a silicon atom by a Si-C bond or a Si-N bond, and examples of these include the above-mentioned examples.

[0081] The hydrolyzed condensate (a6) (polysiloxane) of the hydrolyzable silane (a4) represented by formula (1) or formula (1-1), or the hydrolyzed condensate (polysiloxane) of the hydrolyzable silane containing the hydrolyzable silane (a4) represented by formula (1) or formula (1-1) and the hydrolyzable silane (b) represented by formula (2) and / or formula (3), can have a weight average molecular weight of 500 to 1,000,000, or 1,000 to 100,000. These molecular weights are the molecular weights obtained by polystyrene conversion based on GPC analysis and PEG / PEO conversion based on GFC (aqueous GPC) analysis. The GPC measurement conditions are, for example, a GPC apparatus (product name HLC-8220GPC, manufactured by Tosoh Corporation), a GPC column (product names Shodex KF803L, KF802, KF801, manufactured by Showa Denko K.K.), a column temperature of 40°C, an eluent (elution solvent) of tetrahydrofuran, a flow rate (flow velocity) of 1.0 ml / min, and a standard sample of polystyrene (manufactured by Showa Denko K.K.). The GFC measurement conditions are, for example, a GFC apparatus (product name: RID-10A, manufactured by Shimadzu Corporation), a GFC column (product name: Shodex SB-803HQ, manufactured by Showa Denko K.K.), a column temperature of 40°C, an eluent (elution solvent) of water and 0.5 M acetic acid / 0.5 M sodium nitrate aqueous solution, a flow rate (flow velocity) of 1.0 ml / min, and standard samples of pullulan and PEG / PEO (manufactured by Showa Denko K.K.).

[0082] The hydrolysis of an alkoxysilyl group, an acyloxysilyl group, or a halogenated silyl group may include the following steps: From 0.5 to 100 moles, preferably from 1 to 10 moles, of water are used per mole of hydrolyzable group. The hydrolysis can be carried out using a hydrolysis catalyst or without a hydrolysis catalyst. When a hydrolysis catalyst is used, 0.001 to 10 moles, preferably 0.001 to 1 mole, of the hydrolysis catalyst can be used per mole of the hydrolyzable group. The reaction temperature for carrying out the hydrolysis and condensation is usually 20 to 110°C. The hydrolysis may be complete or partial, that is, hydrolyzates and monomers may remain in the hydrolysis condensate. A catalyst can be used in the hydrolysis and condensation.

[0083] The hydrolysis catalyst may include a metal chelate compound, an organic acid, an inorganic acid, an organic base, and an inorganic base. Metal chelate compounds as hydrolysis catalysts include, for example, triethoxy mono(acetylacetonate)titanium, tri-n-propoxy mono(acetylacetonate)titanium, tri-i-propoxy mono(acetylacetonate)titanium, tri-n-butoxy mono(acetylacetonate)titanium, tri-sec-butoxy mono(acetylacetonate)titanium, tri-t-butoxy mono(acetylacetonate)titanium, diethoxy bis(acetylacetonate)titanium, di-n-propoxy bis(acetylacetonate)titanium, di -i-propoxy bis(acetylacetonate) titanium, di-n-butoxy bis(acetylacetonate) titanium, di-sec-butoxy bis(acetylacetonate) titanium, di-t-butoxy bis(acetylacetonate) titanium, monoethoxy tris(acetylacetonate) titanium, mono-n-propoxy tris(acetylacetonate) titanium, mono-i-propoxy tris(acetylacetonate) titanium, mono-n-butoxy tris(acetylacetonate) titanium, mono-sec-butoxy tris(acetylacetonate) titanium titanium acetate, titanium mono-t-butoxy tris(acetylacetonate), titanium tetrakis(acetylacetonate), titanium triethoxy mono(ethylacetoacetate), titanium tri-n-propoxy mono(ethylacetoacetate), titanium tri-i-propoxy mono(ethylacetoacetate), titanium tri-n-butoxy mono(ethylacetoacetate), titanium tri-sec-butoxy mono(ethylacetoacetate), titanium tri-t-butoxy mono(ethylacetoacetate), titanium diethoxy bis(ethoxy) di-n-propoxy bis(ethylacetoacetate) titanium, di-i-propoxy bis(ethylacetoacetate) titanium, di-n-butoxy bis(ethylacetoacetate) titanium, di-sec-butoxy bis(ethylacetoacetate) titanium, di-t-butoxy bis(ethylacetoacetate) titanium, monoethoxy tris(ethylacetoacetate) titanium, mono-n-propoxy tris(ethylacetoacetate) titanium, mono-i-propoxy tris(ethylacetoacetate) titanium,Mono-n-butoxy tris(ethylacetoacetate)titanium, mono-sec-butoxy tris(ethylacetoacetate)titanium, mono-t-butoxy tris(ethylacetoacetate)titanium, tetrakis(ethylacetoacetate)titanium, mono(acetylacetonato) tris(ethylacetoacetate)titanium, bis(acetylacetonato) bis(ethylacetoacetate)titanium, tris(acetylacetonato) mono(ethylacetoacetate)titanium, and other titanium chelate compounds; triethoxy mono(acetylacetonato)zirconium, tri-n-propoxy Mono(acetylacetonate)zirconium, tri-i-propoxy mono(acetylacetonate)zirconium, tri-n-butoxy mono(acetylacetonate)zirconium, tri-sec-butoxy mono(acetylacetonate)zirconium, tri-t-butoxy mono(acetylacetonate)zirconium, diethoxy bis(acetylacetonate)zirconium, di-n-propoxy bis(acetylacetonate)zirconium, di-i-propoxy bis(acetylacetonate)zirconium, di-n-butoxy bis(acetylacetonate)zirconium, Di-sec-butoxy bis(acetylacetonate)zirconium, di-t-butoxy bis(acetylacetonate)zirconium, monoethoxy tris(acetylacetonate)zirconium, mono-n-propoxy tris(acetylacetonate)zirconium, mono-i-propoxy tris(acetylacetonate)zirconium, mono-n-butoxy tris(acetylacetonate)zirconium, mono-sec-butoxy tris(acetylacetonate)zirconium, mono-t-butoxy tris(acetylacetonate) Zirconium, tetrakis(acetylacetonate)zirconium, triethoxy mono(ethylacetoacetate)zirconium, tri-n-propoxy mono(ethylacetoacetate)zirconium, tri-i-propoxy mono(ethylacetoacetate)zirconium, tri-n-butoxy mono(ethylacetoacetate)zirconium, tri-sec-butoxy mono(ethylacetoacetate)zirconium, tri-t-butoxy mono(ethylacetoacetate)zirconium, diethoxy bis(ethylacetoacetate)zirconium zirconium, di-n-propoxy bis(ethylacetoacetate) zirconium, di-i-propoxy bis(ethylacetoacetate) zirconium, di-n-butoxy bis(ethylacetoacetate) zirconium, di-sec-butoxy bis(ethylacetoacetate) zirconium, di-t-butoxy bis(ethylacetoacetate) zirconium, monoethoxy tris(ethylacetoacetate) zirconium, mono-n-propoxy tris(ethylacetoacetate) zirconium, mono-i-propoxy tris(ethylacetoacetate acetate)zirconium, mono-n-butoxy tris(ethylacetoacetate)zirconium, mono-sec-butoxy tris(ethylacetoacetate)zirconium, mono-t-butoxy tris(ethylacetoacetate)zirconium, tetrakis(ethylacetoacetate)zirconium, mono(acetylacetonato) tris(ethylacetoacetate)zirconium, bis(acetylacetonato) bis(ethylacetoacetate)zirconium, tris(acetylacetonato) mono(ethylacetoacetate)zirconium,zirconium chelate compounds such as aluminum tris(acetylacetonate)aluminum and aluminum tris(ethylacetoacetate)aluminum; and the like.

[0084] Examples of organic acids usable as hydrolysis catalysts include acetic acid, propionic acid, butanoic acid, pentanoic acid, hexanoic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, oxalic acid, maleic acid, methylmalonic acid, adipic acid, sebacic acid, gallic acid, butyric acid, mellitic acid, arachidonic acid, mykimic acid, 2-ethylhexanoic acid, oleic acid, stearic acid, linoleic acid, linoleic acid, salicylic acid, benzoic acid, p-aminobenzoic acid, p-toluenesulfonic acid, benzenesulfonic acid, monochloroacetic acid, dichloroacetic acid, trichloroacetic acid, trifluoroacetic acid, formic acid, malonic acid, sulfonic acid, phthalic acid, fumaric acid, citric acid, tartaric acid, and trifluoromethanesulfonic acid.

[0085] Examples of inorganic acids as hydrolysis catalysts include hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, and phosphoric acid.

[0086] Examples of the organic base as the hydrolysis catalyst include pyridine, pyrrole, piperazine, pyrrolidine, piperidine, picoline, trimethylamine, triethylamine, monoethanolamine, diethanolamine, dimethylmonoethanolamine, monomethyldiethanolamine, triethanolamine, diazabicyclooctane, diazabicyclononane, diazabicycloundecene, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, etc. Examples of the inorganic base include ammonia, sodium hydroxide, potassium hydroxide, barium hydroxide, calcium hydroxide, etc.

[0087] Specifically, in the present invention, the hydrolyzable silane (a4), or the hydrolyzable silane (a4) and hydrolyzable silane (b) are obtained by hydrolyzing the hydrolyzable silane (a4), or the hydrolyzable silane (a4) and the hydrolyzable silane (b) in the presence of an alkaline substance, particularly in the presence of an organic base, and it is preferable that these hydrolyzates are further condensed to form a hydrolysis condensate (polysiloxane). The alkaline substance here is either an alkaline catalyst added during the hydrolysis of the hydrolyzable silane, or an amino group present in the molecule of the hydrolyzable silane.

[0088] In the case of an amino group present in a hydrolyzable silane molecule, examples of the hydrolyzable silane (a4) represented by the above formula (1) or formula (1-1) include silanes containing an amino group in a side chain.

[0089] When an alkaline catalyst is added, the above-mentioned inorganic bases and organic bases among the hydrolysis catalysts are used, with the organic bases being particularly preferred.

[0090] The hydrolyzate of the hydrolyzable silane is preferably one which has been hydrolyzed in the presence of an alkaline substance.

[0091] The composition may further contain a hydrolyzable silane, a hydrolyzate obtained by hydrolyzing the hydrolyzable silane in the presence of an alkaline substance, or a mixture thereof.

[0092] In addition, the present invention can use silsesquioxane obtained by hydrolyzing silane having three hydrolyzable groups. This silsesquioxane is a hydrolysis condensate (a6) obtained by hydrolyzing and condensing silane having three hydrolyzable groups in the presence of an acidic substance. The acidic substance used here can be an acidic catalyst among the above-mentioned hydrolysis catalysts.

[0093] The hydrolysis condensate (a6) may be a random-type, ladder-type or cage-type silsesquioxane.

[0094] Examples of the organic solvent used in the hydrolysis include aliphatic hydrocarbon solvents such as n-pentane, i-pentane, n-hexane, i-hexane, n-heptane, i-heptane, 2,2,4-trimethylpentane, n-octane, i-octane, cyclohexane, and methylcyclohexane; aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, trimethylbenzene, methylethylbenzene, n-propylbenzene, i-propylbenzene, diethylbenzene, i-butylbenzene, triethylbenzene, di-i-propylbenzene, n-amylnaphthalene, and trimethylbenzene; methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, sec-butanol, t-butanol, n-pentanol, i-pentanol, 2-methylbutanol, sec-pentanol, t-pentanol, 3-methoxybutanol, n-hexanol, 2-methylpentanol, sec-hexanol, t-hex ... monoalcohol solvents such as hexanol, 2-ethylbutanol, sec-heptanol, heptanol-3, n-octanol, 2-ethylhexanol, sec-octanol, n-nonyl alcohol, 2,6-dimethylheptanol-4, n-decanol, sec-undecyl alcohol, trimethylnonyl alcohol, sec-tetradecyl alcohol, sec-heptadecyl alcohol, phenol, cyclohexanol, methylcyclohexanol, 3,3,5-trimethylcyclohexanol, benzyl alcohol, phenylmethylcarbinol, diacetone alcohol, and cresol; ethylene glycol, propylene glycol, 1,3-butylene glycol, pentanediol-2,4, 2-methylpentanediol-2,4, hexanediol-2,5, heptanediol-2,4, 2-ethylhexanediol-1,3, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, polyhydric alcohol solvents such as ethylene glycol and glycerin; ketone solvents such as acetone, methyl ethyl ketone, methyl n-propyl ketone, methyl n-butyl ketone, diethyl ketone, methyl i-butyl ketone, methyl n-pentyl ketone, ethyl n-butyl ketone, methyl n-hexyl ketone, di-i-butyl ketone, trimethylnonanone, cyclohexanone, methylcyclohexanone, 2,4-pentanedione, acetonylacetone, diacetone alcohol, acetophenone, and fenchone; ethyl ether, i-propyl ether, n-butyl ether, n-hexyl ether, 2-ethylhexyl ether, ethylene oxide, 1,2-propylene oxide, dioxolane, 4-methyldioxolane, dioxane, dimethyldioxane, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol diethyl ether, ethylene glycol mono-n-butyl ether, ethylene glycol mono-n-hexyl ether, ethylene ether solvents such as glycol monophenyl ether, ethylene glycol mono-2-ethylbutyl ether, ethylene glycol dibutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol diethyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol di-n-butyl ether, diethylene glycol mono-n-hexyl ether, ethoxytriglycol, tetraethylene glycol di-n-butyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol monomethyl ether, tetrahydrofuran, and 2-methyltetrahydrofuran;Diethyl carbonate, methyl acetate, ethyl acetate, gamma-butyrolactone, gamma-valerolactone, n-propyl acetate, i-propyl acetate, n-butyl acetate, i-butyl acetate, sec-butyl acetate, n-pentyl acetate, sec-pentyl acetate, 3-methoxybutyl acetate, methylpentyl acetate, 2-ethylbutyl acetate, 2-ethylhexyl acetate, benzyl acetate, cyclohexyl acetate, methylcyclohexyl acetate, n-nonyl acetate, methyl acetoacetate, ethyl acetoacetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol mono-n-butyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, propylene acetate Examples of suitable solvents include ester-based solvents such as glycol monobutyl ether, dipropylene glycol monomethyl ether acetate, dipropylene glycol monoethyl ether acetate, glycol diacetate, methoxytriglycol acetate, ethyl propionate, n-butyl propionate, i-amyl propionate, diethyl oxalate, di-n-butyl oxalate, methyl lactate, ethyl lactate, n-butyl lactate, n-amyl lactate, diethyl malonate, dimethyl phthalate, and diethyl phthalate; nitrogen-containing solvents such as N-methylformamide, N,N-dimethylformamide, N,N-diethylformamide, acetamide, N-methylacetamide, N,N-dimethylacetamide, N-methylpropionamide, and N-methylpyrrolidone; sulfur-containing solvents such as dimethyl sulfide, diethyl sulfide, thiophene, tetrahydrothiophene, dimethyl sulfoxide, sulfolane, and 1,3-propane sultone. These solvents can be used alone or in combination of two or more.

[0095] Hydrolyzable silane is hydrolyzed and condensed in a solvent using a catalyst, and the obtained hydrolysis condensation product (polymer) can be subjected to reduced pressure distillation or the like to simultaneously remove the by-product alcohol, the hydrolysis catalyst used, and water. In addition, the acid or base catalyst used in the hydrolysis can be removed by neutralization or ion exchange. In the composition to be applied to the resist pattern of the present invention, an inorganic acid, an organic acid, water, an alcohol, an organic amine, a photoacid generator, a metal oxide, a surfactant, or a combination thereof can be added to stabilize the composition containing the hydrolysis condensation product. can be done.

[0096] Examples of the inorganic acid include hydrochloric acid, nitric acid, sulfuric acid, and phosphoric acid. Examples of the organic acid include oxalic acid, malonic acid, methylmalonic acid, succinic acid, maleic acid, malic acid, tartaric acid, phthalic acid, citric acid, glutaric acid, citric acid, lactic acid, salicylic acid, and methanesulfonic acid. Among them, methanesulfonic acid, oxalic acid, maleic acid, octanoic acid, decanoic acid, octanesulfonic acid, decanesulfonic acid, dodecylbenzenesulfonic acid, phenolsulfonic acid, sulfosalicylic acid, camphorsulfonic acid, nonafluorobutanesulfonic acid, toluenesulfonic acid, cumenesulfonic acid, p-octylbenzenesulfonic acid, p-decylbenzenesulfonic acid, 4-octyl 2-phenoxybenzenesulfonic acid, and 4-carboxybenzenesulfonic acid are preferred. The amount of the acid to be added is 0.5 to 15 parts by mass relative to 100 parts by mass of the condensate (polysiloxane).

[0097] The alcohol to be added is preferably one that is easily dispersed by heating after application, such as methanol, ethanol, propanol, isopropanol, butanol, etc. The amount of alcohol to be added may be 0.001 to 20 parts by mass per 100 parts by mass of the composition to be applied to the resist pattern.

[0098] Examples of the organic amine to be added include aminoethanol, methylaminoethanol, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, N,N,N',N'-tetrapropylethylenediamine, N,N,N',N'-tetraisopropylethylenediamine, N,N,N',N'-tetrabutylethylenediamine, N,N,N',N'-tetraisobutylethylenediamine, N,N,N',N'-tetramethyl-1,2-propylenediamine, and N,N,N',N'-tetraethyl-1,2-propylenediamine. Diamine, N,N,N',N'-tetrapropyl-1,2-propylenediamine, N,N,N',N'-tetraisopropyl-1,2-propylenediamine, N,N,N',N'-tetrabutyl-1,2-propylenediamine, N,N,N',N'-tetraisobutyl-1,2-propylenediamine, N,N,N',N'-tetramethyl-1,3-propylenediamine, N,N,N',N'-tetraethyl-1,3-propylenediamine, N,N,N',N'-tetrapropyl-1,3-propylenediamine, N,N,N',N'-tetraisopropyl -1,3-propylenediamine, N,N,N',N'-tetrabutyl-1,3-propylenediamine, N,N,N',N'-tetraisobutyl-1,3-propylenediamine, N,N,N',N'-tetramethyl-1,2-butylenediamine, N,N,N',N'-tetraethyl-1,2-butylenediamine, N,N,N',N'-tetrapropyl-1,2-butylenediamine, N,N,N',N'-tetraisopropyl-1,2-butylenediamine, N,N,N',N'-tetrabutyl-1,2-butylenediamine, N,N,N',N'-tetraisobutyl N,N,N',N'-tetramethyl-1,3-butylenediamine, N,N,N',N'-tetraethyl-1,3-butylenediamine, N,N,N',N'-tetrapropyl-1,3-butylenediamine, N,N,N',N'-tetraisopropyl-1,3-butylenediamine, N,N,N',N'-tetrabutyl-1,3-butylenediamine, N,N,N',N'-tetraisobutyl-1,3-butylenediamine, N,N,N',N'-tetramethyl-1,4-butylenediamine, N,N,N',N'-tetraethyl-1,Examples of the organic amine include 4-butylenediamine, N,N,N',N'-tetrapropyl-1,4-butylenediamine, N,N,N',N'-tetraisopropyl-1,4-butylenediamine, N,N,N',N'-tetrabutyl-1,4-butylenediamine, N,N,N',N'-tetraisobutyl-1,4-butylenediamine, N,N,N',N'-tetramethyl-1,5-pentylenediamine, and N,N,N',N'-tetraethyl-1,5-pentylenediamine. The amount of the organic amine added may be 0.001 to 20 parts by mass per 100 parts by mass of the composition to be applied to the resist pattern. Examples of the photoacid generator to be added include an onium salt compound, a sulfonimide compound, and a disulfonyldiazomethane compound.

[0099] Examples of the onium salt compounds include iodonium salt compounds such as diphenyliodonium hexafluorophosphate, diphenyliodonium trifluoromethanesulfonate, diphenyliodonium nonafluoronormal butanesulfonate, diphenyliodonium perfluoronormal octanesulfonate, diphenyliodonium camphorsulfonate, bis(4-tert-butylphenyl)iodonium camphorsulfonate, and bis(4-tert-butylphenyl)iodonium trifluoromethanesulfonate; and triphenylsulfonium hexafluoroantimonate, triphenylsulfonium nonafluoronormal butanesulfonate, triphenylsulfonium camphorsulfonate, and Examples of sulfonium salt compounds include triphenylsulfonium trifluoromethanesulfonate, triphenylsulfonium adamantanecarboxylate trifluoroethanesulfonate, triphenylsulfonium p-toluenesulfonate, triphenylsulfonium methanesulfonate, triphenylsulfonium phenolsulfonate, triphenylsulfonium nitrate, triphenylsulfonium maleate, bis(triphenylsulfonium)maleate, triphenylsulfonium hydrochloride, triphenylsulfonium acetate, triphenylsulfonium trifluoroacetate, triphenylsulfonium salicylate, triphenylsulfonium benzoate, and triphenylsulfonium hydroxide.

[0100] Examples of the sulfonimide compound include N-(trifluoromethanesulfonyloxy)succinimide, N-(nonafluoronormalbutanesulfonyloxy)succinimide, N-(camphorsulfonyloxy)succinimide, and N-(trifluoromethanesulfonyloxy)naphthalimide.

[0101] Examples of the disulfonyldiazomethane compound include bis(trifluoromethylsulfonyl)diazomethane, bis(cyclohexylsulfonyl)diazomethane, bis(phenylsulfonyl)diazomethane, bis(p-toluenesulfonyl)diazomethane, bis(2,4-dimethylbenzenesulfonyl)diazomethane, and methylsulfonyl-p-toluenesulfonyldiazomethane.

[0102] The photoacid generator may be used alone or in combination of two or more. When the photoacid generator is used, the proportion is 0.01 to 30 parts by mass, or 0.1 to 20 parts by mass, or 0.5 to 10 parts by mass, based on 100 parts by mass of the condensate (polysiloxane).

[0103] Examples of the surfactant contained in the composition of the present invention include nonionic surfactants, anionic surfactants, cationic surfactants, silicone surfactants, and UV-curable surfactants.

[0104] For example, polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene cetyl ether, and polyoxyethylene oleyl ether; polyoxyethylene alkyl allyl ethers such as polyoxyethylene octyl phenol ether and polyoxyethylene nonyl phenol ether; polyoxyethylene-polyoxypropylene block copolymers; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, sorbitan trioleate, and sorbitan tristearate; polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, and polyoxyethylene sorbitan monostearate; Nonionic surfactants such as polyoxyethylene sorbitan fatty acid esters such as polyoxyethylene sorbitan trioleate and polyoxyethylene sorbitan tristearate, trade names: F-TOP EF301, EF303, EF352 (manufactured by Tochem Products Co., Ltd.), trade names: Megafac F171, F173, R-08, R-30, R-40, R-40N (manufactured by DIC Corporation), Fluorad FC430, FC431 (manufactured by Sumitomo 3M Limited), trade names: Examples of such surfactants include fluorine-based surfactants such as Asahi Guard AG710, Surflon S-382, SC101, SC102, SC103, SC104, SC105, and SC106 (manufactured by Asahi Glass Co., Ltd.), and silicone-based surfactants such as organosiloxane polymer KP341 (trade name, manufactured by Shin-Etsu Chemical Co., Ltd.), BYK302, BYK307, BYK333, BYK341, BYK345, BYK346, BYK347, and BYK348 (trade names, manufactured by BYK). Examples of the surfactants include cationic surfactants such as distearyldimethylammonium chloride, benzalkonium chloride, benzethonium chloride, cetylpyridinium chloride, hexadecyltrimethylammonium bromide, and dequalinium chloride; anionic surfactants such as octanoate, decanoate, octane sulfonate, decanoic acid sulfonate, palmitate, perfluorobutane sulfonate, and dodecylbenzene sulfonate; and UV-curable surfactants such as BYK307, BYK333, BYK381, BYK-UV-3500, BYK-UV-3510, and BYK-UV-3530 (manufactured by BYK, product names). These surfactants may be used alone or in combination of two or more. When a surfactant is used, the proportion is 0.0001 to 5 parts by mass, or 0.001 to 5 parts by mass, or 0.01 to 5 parts by mass, per 100 parts by mass of the condensate (polyorganosiloxane).

[0105] As a solvent used in the composition to be applied to the resist pattern of the present invention, water is preferably used, and a hydrophilic organic solvent that dissolves in water can also be mixed therein.

[0106] The coating composition containing the pattern-forming polymer of the present invention is brought into contact with the resist surface after mask exposure, and the gaps between the resist patterns are filled with the polymer, thereby preventing the collapse of the resist pattern. After that, the surface in which the gaps between the resist patterns are filled with the polymer is dry etched, and the resist pattern is removed, and the filled polymer becomes a new resist pattern. This can also be called a reverse process.

[0107] In this case, it is preferable to use a combination of the resist and the filled polymer such that the dry etching rate changes depending on the type of gas used for dry etching. For example, when an acrylic resist material is used as the resist, it is preferable to use a polyorganosiloxane material or an inorganic oxide material as the filled polymer.

[0108] In the present invention, after development with a developer after exposure, the resist is coated with a coating composition containing the polymer of the present invention, and the spaces between the resist patterns are filled with a polymer that can form a new pattern in a subsequent process. This makes it possible to fill in the spaces without destroying the original resist pattern, and a fine pattern that will not collapse can be formed by a reverse pattern in the subsequent dry etching process.

[0109] Furthermore, during development with a developer after exposure, the composition (coating liquid) of the present invention can be poured in instead of the developer or rinsing liquid, thereby filling the spaces between the resist patterns with polymer, and a fine pattern can be formed that will not collapse due to the reverse pattern in the subsequent dry etching process.

[0110] If the coating composition applied to the resist pattern completely covers the resist pattern, it is etched back by dry etching to expose the resist surface, and then dry etched with a gas (oxygen-based gas) that has a high etching rate for the resist to reverse the pattern. The pattern can be inverted by

[0111] More specifically, the present invention relates to a method for manufacturing a semiconductor device, comprising the steps of: (1) applying a resist onto a substrate; (2) exposing and developing the resist; (3) applying the composition described above to the resist pattern during or after development; and (4) etching away the resist pattern to reverse the pattern.

[0112] The photoresist used in step (1) is not particularly limited as long as it is sensitive to the light used for exposure. Either a negative photoresist or a positive photoresist can be used. Examples of the photoresist include a positive photoresist made of a novolac resin and a 1,2-naphthoquinone diazide sulfonic acid ester, a chemically amplified photoresist made of a binder having a group that decomposes with an acid to increase the alkaline dissolution rate and a photoacid generator, a chemically amplified photoresist made of a low molecular compound that decomposes with an acid to increase the alkaline dissolution rate of the photoresist, an alkali-soluble binder, and a photoacid generator, and a chemically amplified photoresist made of a binder having a group that decomposes with an acid to increase the alkaline dissolution rate, a low molecular compound that decomposes with an acid to increase the alkaline dissolution rate of the photoresist, and a photoacid generator. Examples of the photoresist include APEX-E (trade name) manufactured by Shipley, PAR710 (trade name) manufactured by Sumitomo Chemical Co., Ltd., and SEPR430 (trade name) manufactured by Shin-Etsu Chemical Co., Ltd. Further, there can be mentioned fluorine-containing polymer photoresists as described in, for example, Proc. SPIE, Vol. 3999, 330-334 (2000), Proc. SPIE, Vol. 3999, 357-364 (2000), and Proc. SPIE, Vol. 3999, 365-374 (2000).

[0113] In addition, the electron beam resist can be either negative or positive. Chemically amplified resists include those made of an acid generator and a binder having a group that decomposes with an acid to change the alkaline dissolution rate, those made of an alkali-soluble binder, an acid generator, and a low molecular weight compound that decomposes with an acid to change the alkaline dissolution rate of the resist, those made of an acid generator, a binder having a group that decomposes with an acid to change the alkaline dissolution rate, and a low molecular weight compound that decomposes with an acid to change the alkaline dissolution rate of the resist, non-chemically amplified resists made of a binder having a group that decomposes with an electron beam to change the alkaline dissolution rate, and those made of a binder having a site that is cut by an electron beam to change the alkaline dissolution rate. When these electron beam resists are used, a resist pattern can be formed in the same way as when a photoresist is used, with an electron beam as the irradiation source.

[0114] After the resist solution is applied, it is baked at a temperature of 70 to 150° C. for a time of 0.5 to 5 minutes, and a resist film thickness in the range of 10 to 1000 nm is obtained. The resist solution, developer, and the coating materials shown below can be coated by spin coating, dipping, spraying, etc., but the spin coating method is particularly preferable. The resist is exposed through a predetermined mask. For exposure, a KrF excimer laser (wavelength 248 nm), an ArF excimer laser (wavelength 193 nm), EUV light (wavelength 13.5 nm), an electron beam, etc. can be used. After exposure, a post-exposure bake (PEB: PostExposureBake) can be performed as necessary. The post-exposure bake is appropriately selected from a heating temperature of 70° C. to 150° C. and a heating time of 0.3 to 10 minutes.

[0115] The method may include a step (1-1) of forming a resist underlayer film on the substrate prior to the step (1). This resist underlayer film has anti-reflection and organic hard mask functions. Specifically, before applying the resist in step (1), a step (1-1) of forming a resist underlayer film on a semiconductor substrate can be carried out, and then a step (1) of forming a resist thereon can be carried out. . In the step (1-1), a resist underlayer film may be formed on a semiconductor substrate, a silicon hard mask may be formed thereon, and a resist may be formed thereon.

[0116] The resist underlayer film used in the above step (1-1) is used to prevent diffuse reflection during exposure of the upper resist layer, and is also used for the purpose of improving adhesion with the resist, and can be, for example, an acrylic resin or a novolac resin. The resist underlayer film can be formed as a coating film with a thickness of 1 to 1000 nm on the semiconductor substrate. The resist underlayer film used in the above step (1-1) is a hard mask using an organic resin, and a material with a high carbon content and a low hydrogen content is used. Examples include polyvinyl naphthalene resin, carbazole novolac resin, phenol novolac resin, and naphthol novolac resin. These can be used to form a coating film with a thickness of 5 to 1000 nm on the semiconductor substrate.

[0117] In addition, the silicon hard mask used in the above step (1-1) can be a polysiloxane obtained by hydrolysis of a hydrolyzable silane. For example, polysiloxanes obtained by hydrolysis of tetraethoxysilane, methyltrimethoxysilane, and phenyltriethoxysilane can be exemplified. These can form a coating with a thickness of 5 to 200 nm on the resist underlayer film.

[0118] In step (2), exposure is performed through a predetermined mask. For exposure, a KrF excimer laser (wavelength 248 nm), an ArF excimer laser (wavelength 193 nm), EUV (wavelength 13.5 nm), or the like can be used. After exposure, postexposure bake can be performed as necessary. The postexposure bake is performed under appropriately selected conditions from a heating temperature of 70°C to 150°C and a heating time of 0.3 to 10 minutes. Next, development is performed with a developer. As a result, for example, when a positive photoresist is used, the photoresist in the exposed portion is removed, and a photoresist pattern is formed.

[0119] Examples of the developing solution include an aqueous solution of an alkali metal hydroxide such as potassium hydroxide or sodium hydroxide, an aqueous solution of a quaternary ammonium hydroxide such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, or choline, or an aqueous solution of an amine such as ethanolamine, propylamine, or ethylenediamine. Furthermore, a surfactant or the like can be added to these developing solutions. The developing conditions are appropriately selected from a temperature of 5 to 50° C. and a time of 10 to 600 seconds.

[0120] In the present invention, an organic solvent can be used as a developer. After exposure, development is performed with the developer (solvent). As a result, when a positive photoresist is used, the photoresist in the unexposed area is removed, and a photoresist pattern is formed.

[0121] Examples of the developing solution include methyl acetate, butyl acetate, ethyl acetate, isopropyl acetate, amyl acetate, isoamyl acetate, ethyl methoxyacetate, ethyl ethoxyacetate, propylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monopropyl ether acetate, ethylene glycol monobutyl ether acetate, ethylene glycol monophenyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monopropyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monophenyl ether acetate, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, 2-methoxybutyl acetate, 3-methoxybutyl acetate, 4-methoxybutyl acetate, 3-methyl- 3-Methoxybutyl acetate, 3-ethyl-3-methoxybutyl acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, 2-ethoxybutyl acetate, 4-ethoxybutyl acetate, 4-propoxybutyl acetate, 2-methoxypentyl acetate, 3-methoxypentyl acetate, 4-methoxypentyl acetate, 2-methyl-3-methoxypentyl acetate, 3-methyl-3-methoxypentyl acetate, 3-methyl-4-methoxypentyl acetate, 4-methyl-4-methoxypentyl acetate, propylene Examples of the developer include ethylene glycol diacetate, methyl formate, ethyl formate, butyl formate, propyl formate, ethyl lactate, butyl lactate, propyl lactate, ethyl carbonate, propyl carbonate, butyl carbonate, methyl pyruvate, ethyl pyruvate, propyl pyruvate, butyl pyruvate, methyl acetoacetate, ethyl acetoacetate, methyl propionate, ethyl propionate, propyl propionate, isopropyl propionate, methyl 2-hydroxypropionate, ethyl 2-hydroxypropionate, methyl-3-methoxypropionate, ethyl-3-methoxypropionate, ethyl-3-ethoxypropionate, and propyl-3-methoxypropionate. Furthermore, surfactants and the like can be added to these developers. The development conditions are appropriately selected from a temperature of 5 to 50° C. and a time of 10 to 600 seconds.

[0122] In step (3), the coating composition of the present invention is applied to the resist during or after development. In step (3), the coating composition can be heated to form a coating film. Heating is performed at a baking temperature of 50 to 180° C. for 0.5 to 5 minutes. In the present invention, the process may include a step (3-1) of etching back the surface of the coating film formed after the step (3) to expose the surface of the resist pattern. As a result, in the subsequent step (4), the surface of the resist pattern and the surface of the coating composition coincide with each other, and due to the difference in the gas etching rate between the resist pattern and the coating composition, only the resist components are removed, and the components of the coating composition remain, resulting in inversion of the pattern. In the etch-back, the resist pattern is exposed by a gas (e.g., a fluorine-based gas) that can remove the coating composition.

[0123] In step (4), the resist pattern is etched away to reverse the pattern. In step (4), dry etching is performed using a gas such as tetrafluoromethane, perfluorocyclobutane (C4F8), perfluoropropane (C3F8), trifluoromethane, carbon monoxide, argon, oxygen, nitrogen, sulfur hexafluoride, difluoromethane, nitrogen trifluoride, or chlorine trifluoride. In particular, dry etching is preferably performed using an oxygen-based gas. This removes the original resist pattern, and a reverse pattern is formed by the pattern reversal forming component (component (A)) contained in the coating composition.

[0124] The composition to be applied to a resist pattern of the present invention can also be applied onto a patterned resist underlayer film.

[0125] That is, the method for producing a semiconductor device includes the steps of: (a) forming a resist underlayer film on a substrate; (b) forming a hard mask thereon; (c) forming a resist film thereon; (d) forming a resist pattern by exposure to light or an electron beam and development; (e) etching the hard mask using the resist pattern; (f) etching the resist underlayer film using the patterned hard mask; (g) applying the coating composition of the present invention to the patterned resist underlayer film; and (h) etching and removing the resist underlayer film to invert the pattern.

[0126] The resist underlayer film used here is a hard mask using the above-mentioned organic resin, and the hard mask used is a silicon-based hard mask using polysiloxane, which is a hydrolysis condensation product of silane. The hard mask is a resist patterned hard mask. In step (e), the hard mask is etched using a fluorine-based gas. In step (f), the resist underlayer film is etched using an oxygen-based gas. In step (h), the resist underlayer film is etched away to reverse the pattern, and etching using an oxygen-based gas is also used.

[0127] In step (g), the coating composition can be heated to form a coating film. Heating is carried out at a baking temperature of 50 to 500° C. for 0.5 to 5 minutes. In the present invention, the process may include a process of etching back the coating film surface to expose the resist pattern surface after the process (g). As a result, in the subsequent process (h), the resist underlayer film surface and the coating composition surface coincide with each other, and due to the difference in the gas etching rate between the resist underlayer film pattern and the coating composition, only the resist underlayer film components are removed, and the components of the coating composition remain, resulting in pattern inversion. In the above-mentioned etch back, the resist underlayer film pattern is exposed by a gas (e.g., a fluorine-based gas) that can remove the coating composition. EXAMPLES

[0128] (Synthesis Example 1-1) 1.53g of 35% by mass tetraethylammonium hydroxide aqueous solution, 4.89g of water, and 120.54g of tetrahydrofuran were placed in a 500ml flask, and 40.18g of aminopropyltriethoxysilane (100 mol% of the total silane) was added dropwise to the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 241.08g of water was added to the reaction solution, and the reaction by-products ethanol, tetrahydrofuran, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-1-1).

[0129] (Synthesis Example 2-1) 5.89g of water and 120.54g of tetrahydrofuran were placed in a 500ml flask, and 40.18g of aminopropyltriethoxysilane (100 mol% of the total silane) was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 120.54g of water was added to the reaction solution, and the reaction by-products ethanol, tetrahydrofuran, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-1-1).

[0130] (Synthesis Example 3-1) 1.73g of 35% by mass tetraethylammonium hydroxide aqueous solution, 5.54g of water, and 128.58g of tetrahydrofuran were placed in a 500ml flask, and 31.86g of aminopropyltriethoxysilane (70 mol% in total silanes) and 11.0g of triethoxymethylsilane (30 mol% in total silanes) were dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 257.16g of water was added to the reaction solution, and the reaction by-products ethanol, tetrahydrofuran, and water were distilled off under reduced pressure, and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-2-1).

[0131] (Synthesis Example 4-1) 1.81g of 35% by mass tetraethylammonium hydroxide aqueous solution, 5.80g of water, and 131.76g of tetrahydrofuran were placed in a 500ml flask, and 28.58g of aminopropyltriethoxysilane (60 mol% in total silanes) and 15.34g of triethoxymethylsilane (40 mol% in total silanes) were dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 263.52g of water was added to the reaction solution, and the reaction by-products ethanol, tetrahydrofuran, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-2-1).

[0132] (Synthesis Example 5-1) 1.35g of 35% by mass tetraethylammonium hydroxide aqueous solution, 4.34g of water, and 93.38g of tetrahydrofuran were placed in a 500ml flask, and 31.13g of trimethoxy[3-(methylamino)propyl]silane (100 mol% of the total silane) was added dropwise to the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and the reaction was allowed to proceed for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 172.40g of water was added to the reaction solution, and the reaction by-products ethanol, tetrahydrofuran, and water were distilled off under reduced pressure, and the mixture was concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water), and the solid residue at 140°C was calculated to be 20% by mass. The obtained polymer corresponded to the formula (2-3-1).

[0133] (Synthesis Example 6-1) 1.22g of 35% by mass tetraethylammonium hydroxide aqueous solution, 3.90g of water, and 89.99g of tetrahydrofuran were placed in a 500ml flask, and 30.00g of 3-(N,N-dimethylaminopropyl)trimethoxysilane (100 mol% of the total silane) was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and the reaction was allowed to proceed for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 179.98g of water was added to the reaction solution, and the reaction by-products ethanol, tetrahydrofuran, and water were distilled off under reduced pressure, and the mixture was concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-4-1).

[0134] (Synthesis Example 7-1) 1.10g of 35% by mass tetraethylammonium hydroxide aqueous solution, 3.52g of water, and 87.06g of tetrahydrofuran were placed in a 500ml flask, and 29.02g of 3-(2-aminoethylamino)propyltrimethoxysilane (100 mol% of the total silane) was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 174.12g of water was added to the reaction solution, and the reaction by-products ethanol, THF, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-5-1).

[0135] (Synthesis Example 8-1) 1.03g of 35% by mass tetraethylammonium hydroxide aqueous solution, 3.30g of water, and 100.86g of tetrahydrofuran were placed in a 500ml flask, and 33.62g of N-(3-triethoxysilylpropyl)-4,5-dihydroimidazole (100 mol% in total silane) was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 201.72g of water was added to the reaction solution, and the reaction by-products ethanol, THF, and water were distilled off under reduced pressure, and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-6-1).

[0136] (Synthesis Example 9-1) 1.06g of 35% by mass tetraethylammonium hydroxide aqueous solution, 3.41g of water, and 86.20g of tetrahydrofuran were placed in a 500ml flask, and 2-(2-pyridylethyl)trimethoxysilane (100 mol% of all silanes) was added dropwise to the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and the reaction was allowed to proceed for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 172.40g of water was added to the reaction solution, and the reaction by-products ethanol, THF, and water were distilled off under reduced pressure, and the mixture was concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water), and the solid residue at 140°C was calculated to be 20% by mass. The obtained polymer corresponded to the formula (2-7-1).

[0137] (Comparative Synthesis Example 1-1) 2.51g of 35% by mass tetraethylammonium hydroxide aqueous solution, 8.04g of water, and 159.39g of tetrahydrofuran were placed in a 500ml flask, and 53.13g of triethoxymethylsilane (100 mol% of the total silane) was added dropwise to the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and the reaction was allowed to proceed for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 318.77g of water was added to the reaction solution, and the reaction by-products ethanol, THF, and water were distilled off under reduced pressure, and the solution was concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane), which was cloudy.

[0138] (Reference synthesis example 1-1) 2.48g of 35% by mass tetraethylammonium hydroxide aqueous solution, 7.93g of water, and 158.13g of tetrahydrofuran were placed in a 500ml flask, and 1.30g of aminopropyltriethoxysilane (2 mol% in total silanes) and 51.41g of triethoxymethylsilane (98 mol% in total silanes) were dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 316.25g of water was added to the reaction solution, and the reaction by-products ethanol, THF, and water were distilled off under reduced pressure, and the solution was concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane), which was cloudy.

[0139] (Synthesis Example 1-2) 3.82g of 35% by mass tetraethylammonium hydroxide aqueous solution, 3.41g of water, and 120.54g of acetone were placed in a 500ml flask, and 40.18g of aminopropyltriethoxysilane (100 mol% of all silanes) was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. Then, 9.08g of 1M nitric acid aqueous solution was added. After the addition, the flask was transferred to an oil bath adjusted to 40°C and reacted for 240 minutes. Then, the reaction solution was cooled to room temperature, and 241.08g of water was added to the reaction solution, and the reaction by-products ethanol, acetone, and water were distilled off under reduced pressure and concentrated to obtain an aqueous hydrolysis condensate (polysiloxane). Further water was added to make the solvent ratio of water 100% (solvent only water), and 14 The content was adjusted to 20 mass percent in terms of solid residue at 0° C. The resulting polymer corresponded to the formula (2-1-2).

[0140] (Synthesis Example 2-2) 5.89g of water and 120.54g of acetone were placed in a 500ml flask, and 40.18g of aminopropyltriethoxysilane (100 mol% of all silanes) was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. Then, 9.08g of 1M aqueous nitric acid solution was added. After the addition, the flask was transferred to an oil bath adjusted to 40°C and reacted for 240 minutes. Then, the reaction solution was cooled to room temperature, and 241.08g of water was added to the reaction solution, and the reaction by-products ethanol, acetone, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio of 100% water (solvent only water) to 20 mass percent in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-1-2).

[0141] (Synthesis Example 3-2) 5.89g of water and 120.54g of acetone were placed in a 500ml flask, and 40.18g of aminopropyltriethoxysilane was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. Then, 9.08g of 1M aqueous hydrochloric acid was added. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Then, the reaction solution was cooled to room temperature, and 241.08g of water was added to the reaction solution, and the reaction by-products ethanol, acetone, and water were distilled under reduced pressure and concentrated to obtain an aqueous hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-2-2).

[0142] (Synthesis Example 4-2) 5.89g of water and 120.54g of acetone were placed in a 500ml flask, and 40.18g of aminopropyltriethoxysilane was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. Then, 9.08g of 1M acetic acid aqueous solution was added. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Then, the reaction solution was cooled to room temperature, and 241.08g of water was added to the reaction solution, and the reaction by-products ethanol, acetone, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-3-2).

[0143] (Synthesis Example 5-2) 5.89g of water and 120.54g of acetone were placed in a 500ml flask, and 40.18g of aminopropyltriethoxysilane was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. Then, 9.08g of 1M maleic acid aqueous solution was added. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Then, the reaction solution was cooled to room temperature, and 241.08g of water was added to the reaction solution, and the reaction by-products ethanol, acetone, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-4-2).

[0144] (Synthesis Example 6-2) 5.89 g of water and 120.54 g of acetone were placed in a 500 ml flask, and the mixture was stirred with a magnetic stirrer while adding 40.18 g of aminopropyltriethoxysilane. was added dropwise to the mixed solution. Then, 9.08 g of 1M nitric acid aqueous solution and 1.82 g of 1M nonafluorobutanesulfonic acid aqueous solution were added. After the addition, the flask was transferred to an oil bath adjusted to 40°C and reacted for 240 minutes. Then, the reaction solution was cooled to room temperature, 241.08 g of water was added to the reaction solution, and the reaction by-products ethanol, acetone, and water were distilled off under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20 mass percent in terms of solid residue at 140°C. The obtained polymer corresponded to the formula (2-5-2).

[0145] (Synthesis Example 7-2) 5.80g of water and 131.76g of acetone were placed in a 500ml flask, and 28.58g of aminopropyltriethoxysilane and 15.34g of methyltriethoxysilane were dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. Then, 10.76g of 1M aqueous nitric acid solution was added. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Then, the reaction solution was cooled to room temperature, and 263.52g of water was added to the reaction solution, and the reaction by-products ethanol, acetone, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-6-2).

[0146] (Synthesis Example 8-2) 5.22g of water and 93.38g of acetone were placed in a 500ml flask, and 31.13g of methylaminopropyltriethoxysilane was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. Then, 8.05g of 1M aqueous nitric acid solution was added. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Then, the reaction solution was cooled to room temperature, and 186.77g of water was added to the reaction solution, and the reaction by-products ethanol, acetone, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-7-2).

[0147] (Synthesis Example 9-2) 6.83g of water and 86.20g of acetone were placed in a 500ml flask, and 28.73g of pyridylethyltrimethoxysilane was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. Then, 6.32g of 1M aqueous nitric acid solution was added. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Then, the reaction solution was cooled to room temperature, and 172.40g of water was added to the reaction solution, and the reaction by-products methanol, acetone, and water were distilled under reduced pressure and concentrated to obtain an aqueous hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to the formula (2-8-2).

[0148] (Synthesis Example 10-2) 4.69g of water and 89.99g of acetone were placed in a 500ml flask, and 30.00g of dimethylaminopropyltrimethoxysilane was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. Then, 7.23g of 1M aqueous nitric acid solution was added. After the addition, the flask was transferred to an oil bath adjusted to 40°C and reacted for 240 minutes. Then, the reaction solution was cooled to room temperature, and 179.98g of water was added to the reaction solution, and the reaction by-products methanol, acetone, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer was of the formula The result was (2-9-2).

[0149] (Synthesis Example 11-2) 91.16g of water was placed in a 500ml flask, and 22.23g of dimethylaminopropyltrimethoxysilane and 8.16g of triethoxysilylpropylsuccinic anhydride were dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Then, the reaction solution was cooled to room temperature, and 91.16g of water was added to the reaction solution, and the reaction by-products, methanol and water, were distilled off under reduced pressure, and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water), and the solid residue at 140°C was calculated to be 20% by mass. The obtained polymer corresponded to the formula (2-10-2).

[0150] (Synthesis Example 12-2) 92.63g of water was placed in a 500ml flask, and 12.51g of dimethylaminopropyltrimethoxysilane and 18.37g of triethoxysilylpropylsuccinic anhydride were dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. Then, 8.05g of 1M nitric acid aqueous solution was added. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Then, the reaction solution was cooled to room temperature, and 92.63g of water was added to the reaction solution, and the reaction by-products ethanol and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio of 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to the formula (2-10-2).

[0151] (Synthesis Example 13-2) 90.19g of water was placed in a 500ml flask, and 21.54g of dimethylaminopropyltrimethoxysilane and 8.53g of triethoxysilylnorbornanedicarboxylic anhydride were dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Then, the reaction solution was cooled to room temperature, and 90.19g of water was added to the reaction solution, and the reaction by-products ethanol and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to the formula (2-11-2).

[0152] (Synthesis Example 14-2) 92.38g of water was placed in a 500ml flask, and 23.10g of dimethylaminopropyltrimethoxysilane and 7.70g of triethoxysilylethyl gamma-butyrolactone were dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 92.38g of water was added to the reaction solution, and the reaction by-products ethanol and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to the formula (2-12-2).

[0153] (Synthesis Example 15-2) 93.70 g of water was placed in a 500 ml flask, and 22.41 g of methylaminopropyltrimethoxysilane and 8.82 g of triethoxysilylpropylsuccinic anhydride were added dropwise to the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the temperature was adjusted to 40° C. The flask was transferred to a heated oil bath and reacted for 240 minutes. The reaction solution was then cooled to room temperature, and 93.70 g of water was added to the reaction solution. The reaction by-products, ethanol and water, were removed under reduced pressure, and the solution was concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent containing only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer was equivalent to the formula (2-13-2).

[0154] (Synthesis Example 16-2) 85.00g of water was placed in a 500ml flask, and 22.78g of dimethylaminopropyltrimethoxysilane and 8.82g of a 30% aqueous solution of trihydroxysilylpropylsulfonic acid were dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Then, the reaction solution was cooled to room temperature, and 85.00g of water was added to the reaction solution, and the reaction by-products ethanol and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to the formula (2-14-2).

[0155] (Synthesis Example 17-2) 75.93g of water was placed in a 500ml flask, and 25.31g of N-trimethoxysilylpropyldimethylammonium propylsulfonate was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Then, the reaction solution was cooled to room temperature, and 75.93g of water was added to the reaction solution, and the reaction by-products ethanol and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to the formula (2-15-2).

[0156] (Synthesis Example 1-3) 10.12g of 35% by mass tetraethylammonium hydroxide aqueous solution, 1.22g of water, and 140.26g of tetrahydrofuran were placed in a 1000ml flask, and 93.50g of 50% ethanol solution of hydroxymethyltriethoxysilane (100 mol% in total silane) was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 280.51g of water was added to the reaction solution, and the reaction by-products ethanol, tetrahydrofuran, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio of 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-1-3).

[0157] (Synthesis Example 2-3) 84.64g of water was placed in a 1000ml flask, and 37.62g of 75% N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane methanol solution (100 mol% of the total silane) was dropped into the mixed solution while stirring the solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 110°C and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 169.28g of water was added to the reaction solution, and the reaction by-products ethanol, tetrahydrofuran, and water were distilled off under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20 mass percent in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-2-3).

[0158] (Synthesis Example 3-3) 5.00g of 35% by mass tetraethylammonium hydroxide aqueous solution, 0.60g of water, and 84.64g of tetrahydrofuran were placed in a 1000ml flask, and 37.62g of 75% N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane methanol solution (100 mol% of the total silane) was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 169.28g of water was added to the reaction solution, and the reaction by-products ethanol, tetrahydrofuran, and water were distilled under reduced pressure and concentrated to obtain an aqueous hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-2-3).

[0159] (Synthesis Example 4-3) 1.53g of 35% by mass tetraethylammonium hydroxide aqueous solution, 0.18g of water, and 72.10g of tetrahydrofuran were placed in a 1000ml flask, and 48.07g of 50% ethanol solution of [hydroxy(polyethyleneoxy)propyl]triethoxysilane (8-12EO) (100 mol% of total silane) manufactured by Gelest was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 144.20g of water was added to the reaction solution, and the reaction by-products ethanol, tetrahydrofuran, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The resulting polymer corresponded to formula (2-3-3).

[0160] (Synthesis Example 5-3) 5.03g of 35% by mass tetraethylammonium hydroxide aqueous solution, 0.61g of water, and 84.80g of tetrahydrofuran were placed in a 1000ml flask, and 28.27g of (3-glycidoxypropyl)trimethoxysilane (100 mol% of all silanes) was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and the reaction was allowed to proceed for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 19.93g of 1M nitric acid and 169.59g of water were added to the reaction solution, and the reaction by-products methanol, tetrahydrofuran, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-4-3).

[0161] (Synthesis Example 6-3) 4.75g of 35% by mass tetraethylammonium hydroxide aqueous solution, 0.57g of water, and 97.63g of tetrahydrofuran were placed in a 1000ml flask, and 32.54g of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (100 mol% of the total silane) was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 18.80g of 1M nitric acid and 195.27g of water were added to the reaction solution, and the reaction by-products methanol, tetrahydrofuran, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-5-3).

[0162] (Synthesis Example 7-3) 64.92g of 35% by mass tetraethylammonium hydroxide aqueous solution and 91.99g of tetrahydrofuran were placed in a 1000ml flask, and 30.66g of 3-chloropropyltrimethoxysilane (100 mol% of all silanes) was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 183.97g of water was added to the reaction solution, and the reaction by-products methanol, tetrahydrofuran, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-6-3).

[0163] (Synthesis Example 8-3) 48.34g of 35% by mass tetraethylammonium hydroxide aqueous solution and 83.82g of tetrahydrofuran were placed in a 1000ml flask, and 27.94g of 3-bromopropyltrimethoxysilane (100 mol% of all silanes) was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 167.64g of water was added to the reaction solution, and the reaction by-products methanol, tetrahydrofuran, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-6-3).

[0164] (Synthesis Example 9-3) 38.06g of 35% by mass tetraethylammonium hydroxide aqueous solution and 78.75g of tetrahydrofuran were placed in a 1000ml flask, and 26.25g of 3-iodopropyltrimethoxysilane (100 mol% of the total silane) was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 157.51g of water was added to the reaction solution, and the reaction by-products methanol, tetrahydrofuran, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-6-3).

[0165] (Synthesis Example 10-3) 82.86g of 35% by mass tetraethylammonium hydroxide aqueous solution and 100.83g of tetrahydrofuran were placed in a 1000ml flask, and 33.61g of chloromethyltrimethoxysilane (100 mol% of the total silane) was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 201.66g of water was added to the reaction solution, and the reaction by-products methanol, tetrahydrofuran, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-1-3).

[0166] (Synthesis Example 11-3) 101.24 g of a 35% by mass aqueous solution of tetraethylammonium hydroxide and 140.23 g of tetrahydrofuran were placed in a 1000 ml flask, and 46.74 g of acetoxymethyltrimethoxysilane (100 mol % of all silanes) was added dropwise to the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 280.45 g of water was added to the reaction solution to reduce the amount of reaction by-products such as methanol, tetrahydrofuran, and water. The mixture was distilled under reduced pressure and concentrated to obtain an aqueous solution of a hydrolysis condensation product (polysiloxane). Water was further added to adjust the solvent ratio to 100% water (solvent containing only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer was equivalent to the formula (2-1-3).

[0167] (Synthesis Example 12-3) 86.62g of 35% by mass tetraethylammonium hydroxide aqueous solution and 128.63g of tetrahydrofuran were placed in a 1000ml flask, and 42.88g of acetoxyethyltrimethoxysilane (100 mol% of the total silane) was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 257.27g of water was added to the reaction solution, and the reaction by-products methanol, tetrahydrofuran, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-7-3).

[0168] (Synthesis Example 13-3) 75.69g of 35% by mass tetraethylammonium hydroxide aqueous solution and 119.98g of tetrahydrofuran were placed in a 1000ml flask, and 39.99g of acetoxypropyltrimethoxysilane (100 mol% of all silanes) was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C, and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 239.97g of water was added to the reaction solution, and the reaction by-products methanol, tetrahydrofuran, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The obtained polymer corresponded to formula (2-6-3).

[0169] (Synthesis Example 14-3) 11.20g of 35% by mass tetraethylammonium hydroxide aqueous solution, 1.35g of water, and 148.80g of tetrahydrofuran were placed in a 1000ml flask, and 51.73g of 50% ethanol solution of hydroxymethyltriethoxysilane (50 mol% in total silanes) and 23.74g of methyltriethoxysilane (50 mol% in total silanes) were dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 40°C and reacted for 240 minutes. Thereafter, the reaction solution was cooled to room temperature, and 297.60g of water was added to the reaction solution, and the reaction by-products methanol, tetrahydrofuran, and water were distilled under reduced pressure and concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane). Further water was added to adjust the solvent ratio of 100% water (solvent only water) to 20% by mass in terms of solid residue at 140°C. The resulting polymer corresponded to formula (2-8-3).

[0170] (Reference synthesis example 1-3) 19.11g of (3-glycidoxypropyl)trimethoxysilane was placed in a 500ml flask, and 80.88g of 1M nitric acid aqueous solution was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 110°C, and reacted for 240 minutes. Then, the reaction solution was cooled to room temperature, and 80.88g of water was added to the reaction solution, and the reaction by-products methanol, water, and nitric acid were distilled off under reduced pressure, and the solution was concentrated to obtain an aqueous solution of hydrolysis condensate (polysiloxane), which was cloudy. The obtained polymer corresponded to formula (2-4-3).

[0171] (Synthesis Example 1-4) Put 93.13 g of 0.5 M hydrochloric acid into a 300 ml flask and apply the mixture to a magnetic While stirring with a stirrer, 6.87 g of aminopropyltriethoxysilane (100 mol % of the total silane) was dropped into the mixed solution. After the addition, the flask was transferred to an oil bath adjusted to 23°C and reacted for 5 days. Then, the reaction by-products ethanol and water were distilled off under reduced pressure, and the mixture was concentrated to obtain a hydrolysis condensation product (polysiloxane). Then, the reaction by-products ethanol and water were distilled off under reduced pressure, and the mixture was concentrated to obtain a hydrolysis condensation product (polysiloxane). Further water was added to adjust the solvent ratio to 100% water (solvent only water) to 20 mass percent in terms of solid residue at 140°C. The obtained polymer corresponds to the ladder-type silsesquioxane of formula (2-1-4), where R was an ammonium chloride propyl group. (R=C3H6NH3 + Cl - ) Then, 6.8 g of anion exchange resin was added to remove the chloride ions. The resulting polymer was a ladder-type silsesquioxane represented by formula (2-1-4), where R was an aminopropyl group. (R=C3H6NH2)

[0172] (Synthesis Example 2-4) 93.13 g of 0.5M trifluoromethanesulfonic acid aqueous solution was placed in a 300 ml flask, and 6.87 g of aminopropyltriethoxysilane (100 mol% in total silanes) was dropped into the mixed solution while stirring the mixed solution with a magnetic stirrer. After the addition, the flask was transferred to an oil bath adjusted to 23 ° C. and reacted for 2 hours. Then, the reaction by-products ethanol and water were distilled under reduced pressure and concentrated to obtain a hydrolysis condensate (polysiloxane). Then, at 50 ° C. and then at 100 ° C., the reaction by-products ethanol and water were distilled under reduced pressure and concentrated to obtain a hydrolysis condensate (polysiloxane). Then, water was added to adjust the solvent ratio of 100% water (solvent only water) to 20 mass percent in terms of solid residue at 140 ° C. The obtained polymer was a cage-type silsesquioxane and corresponded to the formula (2-2-4), where R was an ammonium propyl trifluoromethanesulfonate group. (R=C3H6NH3 + CF3SO3 - ) Then, 6.8 g of anion exchange resin was added to remove trifluoromethanesulfonate ions. The resulting polymer was a cage-type silsesquioxane, which corresponds to the formula (2-2-4), where R was an aminopropyl group. (R=C3H6NH2)

[0173] (Synthesis Example 1-5) 14.97g of 6M hydrochloric acid solution and 177.57g of ultrapure water were placed in a 300ml flask, and while stirring the mixed solution with a magnetic stirrer, 3.72g of dimethylaminopropyltrimethoxysilane (30 mol% in total silanes) was dropped into the mixed solution. After stirring for 5 minutes at room temperature, the aqueous solution was dropped into 8.73g of tetraethoxysilane (70 mol% in total silanes). After the addition, the flask was transferred to an oil bath adjusted to 23°C and reacted for 2 hours. Then, the reaction by-products ethanol and water were distilled under reduced pressure and concentrated to obtain a hydrolysis condensation product (polysiloxane). Then, the reaction by-products ethanol and water were distilled under reduced pressure at 50°C and then 100°C, and concentrated to obtain a hydrolysis condensation product (polysiloxane). Then, water was added to adjust the solvent ratio of 100% water (solvent only water) to 20 mass percent in terms of solid residue at 140°C. The resulting polymer corresponded to formula (2-1-5).

[0174] (Synthesis Example 2-5) To the polymer obtained in Synthesis Example 1-5, 5 g of anion exchange resin was added to remove hydrochloride anions. The obtained polymer corresponded to the formula (2-2-5).

[0175] (Synthesis Example 3-5) 16.64 g of 6M hydrochloric acid solution and 219.58 g of ultrapure water were placed in a 300 ml flask, and 4.42 g of aminopropyltriethoxysilane (30 mol % of the total silane) was added dropwise to the mixed solution while stirring the mixed solution with a magnetic stirrer. After stirring for 5 minutes at room temperature, The aqueous solution was then added dropwise to 9.71 g of tetraethoxysilane (70 mol % of the total silanes). After the addition, the flask was transferred to an oil bath adjusted to 23°C and reacted for 2 hours. Then, the reaction by-products ethanol and water were distilled off under reduced pressure, and the mixture was concentrated to obtain a hydrolysis condensation product (polysiloxane). Then, the reaction by-products ethanol and water were distilled off under reduced pressure at 50°C and then at 100°C, and the mixture was concentrated to obtain a hydrolysis condensation product (polysiloxane). Then, water was added to adjust the solvent ratio to 100% water (solvent containing only water) to 20 mass percent in terms of solid residue at 140°C. The obtained polymer corresponded to the formula (2-3-5).

[0176] (Synthesis Example 4-5) To the polymer obtained in Synthesis Example 3-5, 5 g of anion exchange resin was added to remove hydrochloride anions. The obtained polymer corresponded to the formula (2-4-5).

[0177] (Synthesis Example 5-5) 5.39g of acetic acid and 179.58g of ultrapure water were placed in a 300ml flask, and while stirring the mixed solution with a magnetic stirrer, 3.72g of dimethylaminopropyltrimethoxysilane (30 mol% in total silanes) was dropped into the mixed solution. After stirring for 5 minutes at room temperature, the aqueous solution was dropped into 8.73g of tetraethoxysilane (70 mol% in total silanes). After the addition, the flask was transferred to an oil bath adjusted to 23°C and reacted for 2 hours. Then, the reaction by-products ethanol and water were distilled under reduced pressure and concentrated to obtain a hydrolysis condensate (polysiloxane). Then, the reaction by-products ethanol and water were distilled under reduced pressure at 50°C and then 100°C, and concentrated to obtain a hydrolysis condensate (polysiloxane). Then, water was added to adjust the solvent ratio of 100% water (solvent only water) to 20 mass percent in terms of solid residue at 140°C. The resulting polymer corresponded to formula (2-5-5).

[0178] (Synthesis Example 6-5) To the polymer obtained in Synthesis Example 5-5, 5 g of anion exchange resin was added to remove acetate anions. The obtained polymer corresponded to the formula (2-2-5).

[0179] (Synthesis Example 7-5) 6.0 g of acetic acid and 199.70 g of ultrapure water were placed in a 300 ml flask, and while stirring the mixed solution with a magnetic stirrer, 4.42 g of aminopropyltriethoxysilane (30 mol% in total silanes) was dropped into the mixed solution. After stirring for 5 minutes at room temperature, the aqueous solution was dropped into 9.71 g of tetraethoxysilane (70 mol% in total silanes). After the addition, the flask was transferred to an oil bath adjusted to 23°C and reacted for 2 hours. Then, the reaction by-products ethanol and water were distilled under reduced pressure and concentrated to obtain a hydrolysis condensate (polysiloxane). Then, the reaction by-products ethanol and water were distilled under reduced pressure at 50°C and then at 100°C, and concentrated to obtain a hydrolysis condensate (polysiloxane). Then, water was added to adjust the solvent ratio to 100% water (solvent only water) to 20 mass percent in terms of solid residue at 140°C. The resulting polymer corresponded to formula (2-6-5).

[0180] (Synthesis Example 8-5) To the polymer obtained in Synthesis Example 7-5, 5 g of anion exchange resin was added to remove acetate anions. The obtained polymer corresponded to the formula (2-4-5).

[0181] (Preparation of composition to be applied to resist pattern) The polysiloxane (polymer), inorganic compound, acid, and solvent obtained in the above synthesis examples were mixed in the ratios shown in Tables 1-1 to 1-6, and filtered through a 0.1 μm fluororesin filter to prepare compositions to be applied to resist patterns. The ratio of polymer added in the tables indicates the amount of polymer itself added, not the amount of polymer solution added. Ultrapure water was used as water in the tables. The amount of each added is shown in parts by mass. APTEOS is an aminopropane. Pyrtrimethoxysilane and TPSCS refers to triphenylsulfonium camphorsulfonate. The following inorganic compounds 1 to 7 were prepared as examples of inorganic compounds represented by metal oxide (a1), polyacid (a2), and polyacid salt (a3). Inorganic compound 1 is ammonium metatungstate, inorganic compound 2 is silicotungstic acid, inorganic compound 3 is phosphotungstic acid, inorganic compound 4 is ammonium molybdate, inorganic compound 5 is phosphomolybdic acid, inorganic compound 6 is tungstic acid, and inorganic compound 7 is molybdic acid. Nonionic surfactants refer to surfactants that are not ionic, and polyoxyethylene polyoxypropylene glycol was used. Anionic surfactants refer to surfactants in which the anionic moiety is bonded to the main component, and ammonium palmitate was used. Cationic surfactants refer to surfactants in which the cationic moiety is bonded to the main component, and dodecyltrimethylammonium salt was used as the cationic surfactant. Silicone surfactants refer to surfactants whose main component contains silicon atoms, and BYK331 (trade name, manufactured by BYK) was used. UV-curable surfactants refer to surfactants that have a moiety that polymerizes when exposed to UV light, and BYK333 (trade name, manufactured by BYK) was used. In addition, a PSS-octa[(3-propylglycidyl ether)dimethylsiloxy] substituted product was used as the cage-type PSQ1, a PSS-octa[(3-hydroxypropyl)dimethylsiloxy] substituted product was used as the cage-type PSQ2, and octakis(tetramethylammonium)pentacyclooctasiloxane-octakis(yloxide) hydrate was used as the cage-type PSQ3.

[0182] Furthermore, the aqueous polysiloxane solutions of Comparative Synthesis Example 1-1 and Reference Synthesis Example 1-1 were cloudy and not sufficiently homogeneous, and therefore could not be used as compositions to be applied to the resist patterns of the present invention.

[0183] [Table 1] [Table 2]

[0184] [Table 3] [Table 4]

[0185] [Table 5] [Table 6]

[0186] [Table 7] [Table 8]

[0187] [Table 9] [Table 10]

[0188] (Preparation of Organic Resist Underlayer Film Forming Composition) Under nitrogen, carbazole (6.69g, 0.040mol, manufactured by Tokyo Chemical Industry Co., Ltd.), 9-fluorenone (7.28g, 0.040mol, manufactured by Tokyo Chemical Industry Co., Ltd.), and paratoluenesulfonic acid monohydrate (0.76g, 0.0040mol, manufactured by Tokyo Chemical Industry Co., Ltd.) were added to a 100ml four-neck flask, and 1,4-dioxane (6.69g, manufactured by Kanto Chemical Co., Ltd.) was charged and stirred, and the temperature was raised to 100°C to dissolve and initiate polymerization. After 24 hours, the mixture was allowed to cool to 60°C, and then chloroform (34g, manufactured by Kanto Chemical Co., Ltd.) was added to dilute the mixture, and the mixture was reprecipitated in methanol (168g, manufactured by Kanto Chemical Co., Ltd.). The resulting precipitate was filtered and dried in a vacuum dryer at 80°C for 24 hours to obtain 9.37g of the target polymer (formula (3-1), hereinafter abbreviated as PCzFL). [ka]

[0189] PCzFL 1 The H-NMR measurement results were as follows: 1 H-NMR(400MHz,DMSO-d6):δ7.03-7.55(br,12H),δ7.61-8.10(br,4H),δ11.18(br,1H) The weight average molecular weight Mw of PCzFL measured by GPC in terms of polystyrene was 2,800, and the polydispersity Mw / Mn was 1.77. 20 g of the obtained resin was mixed with 3.0 g of tetramethoxymethyl glycoluril (manufactured by Mitsui Cytec Co., Ltd., product name Powder Link 1174) as a crosslinking agent, 0.30 g of pyridinium paratoluenesulfonate as a catalyst, and 0.06 g of Megafac R-30 (manufactured by Dai Nippon Ink and Chemicals Co., Ltd., product name) as a surfactant, and dissolved in 88 g of propylene glycol monomethyl ether acetate to obtain a solution. Thereafter, the mixture was filtered using a polyethylene microfilter having a pore size of 0.10 μm, and further filtered using a polyethylene microfilter having a pore size of 0.05 μm to prepare a solution of an organic resist underlayer film forming composition for use in a lithography process using a multilayer film.

[0190] (Measurement of dry etching rate) The etcher and etching gas used in the measurement of the dry etching rate were as follows: ES401 (Nippon Scientific): CF4 RIE-10NR (Samco): O2 The composition to be applied to the resist pattern prepared in the examples was applied onto a silicon wafer using a spinner. The composition was heated on a hot plate at 100°C for 1 minute to form a Si-containing coating film (film thickness 0.1 μm (for measuring the etching rate with CF4 gas) and film thickness 0.1 μm (for measuring the etching rate with O2 gas)). Similarly, the organic resist underlayer film forming composition was used to form a coating film (film thickness 0.20 μm) on a silicon wafer using a spinner. The dry etching rate was measured using CF4 gas and O2 gas as etching gases, and was compared with the dry etching rate of the Si-containing coating film prepared in the examples. The results are shown in Tables 2-1 to 2-6.

[0191] [Table 11] [Table 12]

[0192] [Table 13] [Table 14]

[0193] [Table 15] [Table 16]

[0194] [Resist pattern filling by ArF exposure] The organic resist underlayer film forming composition prepared on a silicon substrate was applied using a spinner and heated at 240° C. for 60 seconds to form a resist underlayer film with a thickness of 400 nm, and an ArF resist solution (manufactured by JSR Corporation, product name: AR2772JN) was applied on the film using a spinner. A resist film with a thickness of 210 nm was formed by heating on a hot plate at 110° C. for 90 seconds. The resist film was exposed under predetermined conditions using an ArF excimer laser exposure device (manufactured by Nikon Corporation, S307E). After the above exposure with a target line width of 65 nm and space width of 195 nm, heating (PEB) was performed at 110° C. for 90 seconds, and the silicon substrate was cooled to room temperature on a cooling plate. Thereafter, the resist pattern was formed by development using a 2.38 mass% tetramethylammonium aqueous solution. Next, the coating composition (coating liquid) of the example was applied to this resist pattern, and the 2.38 mass% tetramethylammonium aqueous solution used for development was replaced with this coating composition. After that, the silicon substrate was spun at 1500 rpm for 60 seconds to dry the solvent in the coating composition, and then heated at 100°C for 60 seconds to form a coating film, and the resist pattern was embedded.

[0195] The coating film formed using the coating composition of the example was etched back by dry etching using a mixed gas of CF4 (flow rate 50 sccm) and Ar (flow rate 200 sccm) to expose the upper part of the resist pattern.Then, the resist pattern was removed by dry etching using a mixed gas of O2 (flow rate 10 sccm) and N2 (flow rate 20 sccm) to obtain a reverse pattern. The result of embedding with the coating composition of the embodiment was observed by cross-sectional SEM. Furthermore, the pattern shape of the reverse pattern obtained after dry etching was observed by cross-sectional SEM. Furthermore, as Comparative Example 1, instead of applying the coating composition of the embodiment to the resist pattern after development, the pattern shape of the resist pattern after rinsing after development using pure water as a conventional rinse liquid was observed by cross-sectional SEM. The evaluation results of the embeddability of the pattern and the pattern shape are summarized in Tables 3-1 to 3-6 below. In Tables 3-1 to 3-6, "good" means that the resist pattern was embedded without generating voids in terms of the embeddability, and that the reverse pattern was formed without the pattern collapsing in terms of the pattern shape. In addition, it was confirmed that the photoresist pattern in Comparative Example 1 collapsed.

[0196] [Table 17] [Table 18]

[0197] [Table 19]

[0198] [Table 20] [Table 21] [Table 22] [Industrial Applicability]

[0199] The composition to be applied to the resist pattern of the present invention is applied onto the resist pattern when forming a fine pattern in a lithography process, thereby forming a gap between the patterns. The composition fills the space between the resist patterns, preventing them from collapsing. Furthermore, after drying, a polymer coating film is formed between the resist patterns, and the pattern can be reversed by utilizing the difference in gas etching rate between the resist patterns and the polymer coating film formed between them.

Claims

1. A composition comprising the following components (A) and (B) that is applied to a resist pattern to reverse the pattern by utilizing a difference in gas etching rates: Component (A): hydrolysis condensate (a6) of hydrolyzable silane (a4), (B) component: aqueous solvent, The hydrolyzable silane (a4) has the formula (1): 【Chemistry 1】 (In the formula R 3 represents an organic group having a tertiary amino group and bonded to a silicon atom via a Si-C bond or a Si-N bond, and R 3 may form a ring and be bonded to the Si atom. 1 R represents an organic group having an alkyl group, an aryl group, a halogenated alkyl group, a halogenated aryl group, an alkenyl group, or an epoxy group, an acryloyl group, a methacryloyl group, a mercapto group, or a cyano group, and is bonded to a silicon atom via a Si-C bond. 2 represents an alkoxy group, an acyloxy group, or a halogen group. 0 represents an integer of 0 or 1; 0 represents an integer of 1 to 3; 0 represents an integer of 1 to 2; The hydrolysis condensate (a6) of the hydrolyzable silane (a4) is obtained by hydrolyzing the hydrolyzable silane (a4) in the presence of an alkaline substance or an acidic substance. The composition.

2. 2. The composition according to claim 1, wherein the component (A) further comprises a hydrolyzable silane (a4) and a hydrolyzate of the hydrolyzable silane (a5).

3. 2. The composition according to claim 1, wherein the alkaline substance is an alkaline catalyst added during the hydrolysis of the hydrolyzable silane, or an amino group present within the molecule of the hydrolyzable silane.

4. A hydrolyzable silane (a4) represented by formula (1) and a compound represented by formula (2): 【Chemistry 2】 (In the formula R 4 represents an organic group having an alkyl group, an aryl group, a halogenated alkyl group, a halogenated aryl group, an alkenyl group, an acryloyl group, a methacryloyl group, a mercapto group, or a cyano group, and is bonded to a silicon atom via a Si-C bond; R 5 represents an alkoxy group, an acyloxy group, or a halogen group, and a represents an integer of 0 to 3. 【Chemistry 3】 (In the formula R 6 represents an alkyl group; R 7 represents an alkoxy group, an acyloxy group, or a halogen group, Z represents an alkylene group or an arylene group, b represents an integer of 0 or 1, and c represents an integer of 0 or 1.

5. 5. The composition according to claim 4, wherein the hydrolyzable silane comprises hydrolyzable silane (a4) and hydrolyzable silane (b) in a molar ratio of (a4):(b)=3:97 to 100:

0.

6. The composition according to claim 1, wherein the hydrolysis condensate (a6) of the hydrolyzable silane is a random-type, ladder-type, or cage-type silsesquioxane.

7. The composition according to any one of claims 1 to 6, further comprising an acid or a base.

8. The composition according to any one of claims 1 to 7, further comprising a surfactant.

9. The composition according to claim 1 , further comprising a photoacid generator.

10. 10. A method for manufacturing a semiconductor device, comprising: (1) applying a resist onto a substrate; (2) exposing and developing the resist; (3) applying the composition according to claim 1 to the resist pattern during or after development; and (4) removing the resist pattern by gas etching to invert the pattern.

11. The method according to claim 10, further comprising, before the step (1), a step (1-1) of forming a resist underlayer film on the substrate.

12. The method according to claim 10 or 11, further comprising a step (3-1) of etching back the surface of the coating film formed after the step (3) to expose the surface of the resist pattern.

13. 10. A method for manufacturing a semiconductor device, comprising: a step (a) of forming a resist underlayer film on a substrate; a step (b) of forming a hard mask thereon; a step (c) of further forming a resist film thereon; a step (d) of forming a resist pattern by irradiation with light or an electron beam and development; a step (e) of etching the hard mask using the resist pattern; a step (f) of etching the resist underlayer film using the patterned hard mask; a step (g) of applying the composition according to any one of claims 1 to 9 to the patterned resist underlayer film; and a step (h) of removing the resist underlayer film by gas etching to invert the pattern.

Citation Information

Patent Citations

  • Manufacture of resist structure

    JP1995050286A

  • Pattern forming method and method for manufacturing semiconductor device

    JP2005277052A

  • Pattern forming method

    JP2011027980A

  • Polymer-containing developer

    WO2012128251A1

  • Method for manufacturing semiconductor device using organic underlayer film-forming composition for solvent development lithography processes

    WO2014007079A1